Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Numerical investigation of inorganic fouling on reverse osmosis membranes using optimized bionic spacers: Hydrodynamic mechanisms and predictive modeling - Xiao Hu; Junjie Li; Zuchao Zhu; Sanchuan Yu; Peifeng Lin; Jianzhong Lin (Desalination, 2026)

Targeting EFEMP1 enhances chondrogenesis and inhibits hypertrophic differentiation in a spontaneous osteoarthritis mouse model - Yuhan Chang; Pei-Heng Jiang; Yung-Heng Hsu; Yu-Chih Lin; Chih-Chien Hu; Yi-Zhen Li; Steve Wen-Neng Ueng; Mei-Feng Chen (Journal of Molecular Medicine, 2026)

Correction: Causal Inference for Spatial Cross-Sectional Data: A Geographical Convergent Cross Mapping Method Accounting for Spatial Autocorrelation - Kaixuan Zhang; Xiaoyu Hu; Yehua Sheng; Shifeng Yu; Lin Yang (Journal of Geovisualization and Spatial Analysis, 2026)

Spatial-temporal representation of cortical neural activity evoked by acupuncture stimulation - Haitao Yu; Zhiwen Hu; Zaidong Lin; Jiang Wang; Chen Liu; Jialin Liu; Guiping Li (Cognitive Neurodynamics, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Analysis of the vibration characteristics of liquid droplets in oil induced by CPG electric field with data-driven assistance - Ye Peng; Yaozhong Hu; Haifeng Gong; Lin Yan; Bao Yu; Hong Yin; Ping Ouyang (Journal of Environmental Chemical Engineering, 2026)

Co-degradation detoxification of dichloromethane and n-hexane in a microbial electrolytic cell: metagenomic insights into degradation pathways and functional genes - Meng Wu; Hongfeng Lu; Wenjun Lin; Jun Hu; Zhiliang Yu; Jianming Yu (Journal of Environmental Chemical Engineering, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Breaking biofilm barriers and reprogramming immunity: NIR-activated protease–copper nanozymes drive cuproptosis-like killing and accelerate infected wound repair - Yi Hu; Zijian Hu; Yuting Ding; Yuan Zhou; Duo Zhou; Song Ye; Wei Jiang; Yanbin Zhang; Junhui Song; Chengying Meng; Yu Chen; Yueyang Fang; et al. (Chemical Engineering Journal, 2026)

Interlocking architecture-enabled ultrasensitive iontronic pressure sensor based on [BMIM]BF4-functionalized sponge - Xiaohui Guo; Xiaomeng Yao; Bing Hu; Xinran He; Hongtao Tan; Yaqi Yu; Haining Wang; Jiashu Cao; Zhiyuan Liu; Zhangling Duan; Ting-Jung Lin; Yunong Zhao (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Secondary aerosol formation Would Promote the Formation of Ozone: Evidence from a Yangtze River Delta campaign - Gang Zhao; Jinyuan Yu; Song Guo; Min Hu; Linghan Zeng; Weili Lin; Chunsheng Zhao (Atmospheric Environment, 2026)

Pyridyl ethyl diazoacetate derivatization enables LC-MS annotation of cholesterol and its metabolites - Wenhao Ke; Yikang Wang; Yang Chen; Hanchu Ye; Wen-Di Duan; Feifei Lin; Yingying Wang; Zhengjun Zhou; Zhiyong Yu; Youhong Hu; Jia Liu (Analytica Chimica Acta, 2026)

Corrigendum to “Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol” [Biores. Technol. 390 (2023) 129855] - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2026)

Enhanced degradation of sunscreen additive through oxone activated by cobalt sulfide: Tailoring the nanostructure for boosting catalytic performance - Xin-Yu Jiang; Shaoping Tong; Ta Cong Khiem; Nguyen Nhat Huy; Wei-Jie Liu; Wei-Hsin Chen; Chechia Hu; Kun-Yi Andrew Lin (Journal of Water Process Engineering, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Ultra-high pressure-assisted enzymatic extraction enhances phenolic release and functional potency in fermented dark tea extracts - Xiaoying Lin; Jun Li; Yuanshan Yu; Dengwen Lei; Tenggen Hu; Manqin Fu; Qiang Xiao; Junying Zou; Ya Gao; Chao Huang; Jing Wen (Food Research International, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Integrated thermal insulation and sound absorption in hierarchically architected 3D-printed dual-nanofiber aerogels - Yichao Yu; Yinxiao Jia; Xiaoxiao Lin; Mingkun Zhang; Sisi Wang; Weiling Zhu; Shaohua Jiang; Jiahui Shen; Jiajia Zheng; Zhonglue Hu; Yiming Chen (Chemical Engineering Journal, 2026)

Effects of dietary genistein supplementation in oxidized fish oil feed on growth performance, hepatic lipid metabolism, and intestinal health of juvenile turbots (Scophthalmus maximus L.) - Xiaoqian Zhou; Lin Yang; Junfeng Hu; Yu Gong; Xin Xiao; Zhijie Dan (Animal Feed Science and Technology, 2026)

Dual-color ultrabright AIEgens nanoparticles-based lateral flow immunoassay for simultaneous quantitative detection of serum amyloid A protein and C-reactive protein - Lun Bian; Yuhang Yang; Yu Fu; Kuangrou Jia; Xiangzhou Liu; Xueqing Xu; Yingsong Wu; Fang Hu; Guanfeng Lin (Analytica Chimica Acta, 2026)

Dynamic response of heterogeneously stratified calcareous sand foundations: An integrated experimental-numerical study - Jun Hu; Mengyi Liu; Shuai Zhang; Hanyu Dang; Mingren Lin; Yu Li (Marine Georesources & Geotechnology, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Occurrence and driving factors of microplastics in the surface water of a grassland river in China - Tong Lin; Zeyuan Liu; Qifeng Liu; Ruihong Yu; Haizhu Hu (Journal of Hydrology, 2026)

The luxury effect under environmental filtering: Drivers of residential plant diversity in 15 high-altitude cities - Yao Yao; Zhiwen Gao; Lin He; Luyi Lan; Xiaoya Yu; Ruishen Yang; Junwei Wang; Yuandong Hu; Qiong La; Liangjun Da (Journal of Environmental Management, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Acid-resistant ferrihydrite-spent grain composites for enhanced as and Sb removal from acid mine drainage - Zhongqiang Hu; Zhan Yao; Lin Yu; Jianping Guo; Zhihui Yang; Weichun Yang; Qi Liao; Xi Chen; Shuyan Mi (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Epigallocatechin gallate attenuates free fatty acid-induced hepatocyte apoptosis by restoring endoplasmic reticulum homeostasis - Ran Yu; Yunlong Jiang; Shujing Tan; Junpeng Huang; Dong Hu; Lin Zhou; Muhammad Huraira Waseem; Weiguo Zhao; Chengmin Li (Veterinary Research Communications, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Breaking boundaries: A social–ecological network approach to collaborative governance of soil erosion risk - Yifan Lin; Jian Peng; Zihan Xu; Tao Hu; Xuebang Liu; Hui Tang; Shuying Yu (Ambio, 2026)

Thermal plasticity in the large yellow croaker (Larimichthys crocea): Insights from liver metabolism and gut microbiota under acute thermal stress - Jingan Wang; Yu Liu; Zihan Wang; Jian Yang; Chenhao Hu; Yuan Gao; Xiaohua Wang; Zhihua Lin; Chibo Liu; Kai Zhao (Aquaculture, 2026)

Clean heating transition in China: Technological innovation, residual emission burden, and regional inequality in northern cities - Linyan Li; Yunlong Wu; Li Zhang; Huili Wang; Jieyi Li; Lin Xiang; Xiurong Hu; Jiaxuan He; Ling Jin; Xiaojun Chen; Hui Xu; Yu Lei (Sustainable Production and Consumption, 2026)

Natural antimicrobial composite membranes for effective filtration and inactivation of airborne bacteria and viruses - Guangpeng Yao; Zhijian Liu; Jie Shi; Lina Hu; Mingtao Ding; Chaofan Lin; Wenbin Zhuang; Miao Yu; Junzhou He (Journal of Hazardous Materials, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Embankment protection-inspired interfacial engineering for ultrahigh-efficiency, stable tandem quantum dot light-emitting devices - Kuibao Yu; Zhihan Lin; Tian Liu; Haolin Luo; Chao Zhong; Hao Liu; Fushan Li; Hailong Hu (Chemical Engineering Journal, 2026)

Enhancing Ore Recovery and Profitability Through Blast-Aware Dig-Limit Optimization in Open-Pit Mining - Zhi Yu; Lin-Feng Du; Zong-Xian Zhang; Ming-Qing Huang; Jian-Hua Hu; Jian Zhou; Xing-Qi Cai (Rock Mechanics and Rock Engineering, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Mitochondrial dynamics in environmental neurotoxicity: beyond oxidative stress toward spatial and functional reorganization - Xinyi Yu; Weiqi Lin; Wenqi Hu; Dingxin Long; Weichao Zhao (Archives of Toxicology, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Differential effects of sulfide-induced transformation of biodegradable and conventional microplastics on sedimentary CO2 and CH4 emissions: Underlying microbiome-mediated mechanisms - Jinying Hu; Wenjuan He; Zhexi Liu; Qi Qiao; Lizi Zhao; Yuanyuan Li; Mengyu Ma; Hanbo Yu; Lin Shi; Jinhui Huang (Environmental Research, 2026)

Formation and evolution of sandy deserts in China: A review - Xin Wang; Ziying Yu; Han Hu; Chongwen Luo; Wenjing Yang; Jiayi Lin; Yu Cao; Zaijun Li; Fei Wang; Baofeng Li; Shengqian Chen; Huayu Lu; et al. (Earth-Science Reviews, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Causal Inference for Spatial Cross-Sectional Data: A Geographical Convergent Cross Mapping Method Accounting for Spatial Autocorrelation - Kaixuan Zhang; Xiaoyu Hu; Yehua Sheng; Shifeng Yu; Lin Yang (Journal of Geovisualization and Spatial Analysis, 2026)

Antimicrobial and Antitumor Activities of Endophytic Fungi from the Medicinal Plant Paris polyphylla var. yunnanensis - Jing Zhang; Hao-Lin Yu; Yu Zhang; Chen-Sen Xu; Chao Wang; Yi-Lin Liu; Yi-Bo Shen; Jin-Zhong Hu; Zhi-Xin Liao (Current Microbiology, 2026)

Three-dimensional hierarchical CuCoAl-layered double hydroxide/Ti3C2 Schottky heterojunction for efficient visible-light degradation of ciprofloxacin - Zifei Gao; Ye Liu; Deke Wang; Baoyu Zou; Xingkang Yu; Yu Dong; Qing Li; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong; Jun Hu (Applied Clay Science, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

Efficient Prediction of Fracture Surface Morphology and Analysis of Key Controlling Factors in CAES Tunnel-Type Underground Caverns Based on a Machine Learning Surrogate Model - Shan Lin; Junchen Ding; Wanrui Hu; Guanhua Sun; Jiao Wang; Xianyang Yu; Miao Dong (Rock Mechanics and Rock Engineering, 2026)

Evaluating sustainable coastal management strategies following Spartina alterniflora eradication: Insights from typhoon-induced hydro-sedimentary responses - Lv Gong; Yang Hu; Yuanhao Song; Liangxun Pan; Lin Su; Xiaoyu Yu; Wenzhen Zhao; Ben Li; Xiuzhen Li (Ocean & Coastal Management, 2026)

Quantifying evapotranspiration and shading cooling of urban vegetation across climates under extreme heat using an integrated SCOPE-SEB model and surface temperature analysis - Zhaowu Yu; Mingchuan Shao; Wenjun Yang; Yujia Zhang; Yuxia Hu; Wenjuan Ma; Junhong Zhong; Yanghan Lin; Mincong Wang; Huiwen Zhang; Jiquan Chen; Chenghao Wang; et al. (Remote Sensing of Environment, 2026)

SlCNR promotes the lycopene accumulation and reduces abscisic acid content in postharvest tomato fruit - Shuai Zhang; Mingzhe Mang; Di Chen; Liqun Ma; Shiyuan Zhang; Tingting Hu; Lin Yu; Jiankang Cao; Daqi Fu; Benzhong Zhu; Hongliang Zhu; Guiqin Qu (Postharvest Biology and Technology, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

Green synthesis of glycerol carbonate from glycerol and CO2 using a polymeric ionic liquid catalyst: An experimental and theoretical study - Yi-Lin Lee; Yu-Chi Kao; He-Xiang Xu; Shun Tsunekawa; Masaaki Yoshida; Yi-Pei Li; Chechia Hu (Journal of Cleaner Production, 2026)

Deep eutectic solvent-based ultrasound extraction of bioactive flavonoids from Coreopsis tinctoria Nutt.: Process optimization, HPLC analysis, and preliminary bioactivity evaluation - Peng Wen-Yu; Lin Fang-Qi; Mo Hong-Bo; Hu Tong-Yi; Ou Hong (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Risk evaluation associated with high-temperature disasters in citrus-producing regions of China - Swe Zin Phyo; Siliang Shuai; Lin Zhao; R. M. Dinesh Madhushanka Karunarathna; Ying Yu; Abu Reza Md. Towfiqul Islam; Qi Li; Zhenghua Hu (Theoretical and Applied Climatology, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Lycorine impairs Spodoptera litura fitness by inhibiting secretory phospholipase A2 expression and disrupting lipid homeostasis - Kai Lin; Liuhao Wang; Hu Tian; Shaoyi Wang; Rongyao Zhu; Hao Yu; Lei Yue (Pesticide Biochemistry and Physiology, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Waste lignin-based N/O-rich carbon nanofibers as bifunctional materials for efficient CO2 conversion and energy storage - Wei Hui; Xin Wang; Zao-Lin Hu; Ming-Yu Zhao; Jia-Xin Feng; Wen Chen; Xiao-Yu Xiao; Chuang-Qi Zheng; Lei Pu (Journal of Environmental Chemical Engineering, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

USP7 protects histone H1.2 from proteasome-mediated degradation to facilitate DNA repair and pancreatic neuroendocrine neoplasms progression - Mujie Ye; Lin Xu; Ping Yu; Jialing Pan; Xiaoting Shi; Bingyan Xue; Na He; Ping Hu; Min Liu; Xintong Lu; Yuemei Xu; Yanling Xu; et al. (Science China Life Sciences, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Biofloc Technology Improves Harmful Nitrogen and Pathogens Control and Enhances Production Performance in Intensive Penaeus vannamei Culture Ponds with Reduced Water Exchange - Shuangyin Li; Hongyu Liu; Yiji Lin; Yucheng Cao; Guoliang Wen; Haochang Su; Xiaojuan Hu; Yu Xu; Keng Yang; Wujie Xu (Fishes, 2026)
This 90-day trial evaluated the integrated benefits of biofloc technology (BFT) in lined ponds for intensive Penaeus vannamei culture, comparing it with a conventional water-exchange (WE) system. The BFT system maintained favorable water quality with a 68.4% reduction in cumulative water exchange. Concentrations of toxic total ammonia–nitrogen (TAN) and nitrite–nitrogen (NO2−-N) were better controlled, and total suspended solids (TSS) stabilized within a beneficial range (150–200 mg L−1). Microbial analysis indicated that BFT significantly increased total bacterial abundance in both culture water and shrimp hepatopancreas while reducing the total Vibrio-to-bacteria ratio in culture water to below 6%, significantly lower than in the WE system (>18%). Moreover, BFT significantly lowered the loads of specific pathogens, acute hepatopancreatic necrosis disease (AHPND)-causing Vibrio parahaemolyticus, and Enterocytozoon hepatopenaei (EHP) in both culture water and shrimp hepatopancreas. Regarding production performance, BFT significantly enhanced shrimp survival rate (82.4% vs. 71.5%), yield (3460 vs. 2948 kg pond−1), and water productivity (0.85 vs. 0.28 kg m−3), while lowering the feed conversion ratio (1.16 vs. 1.33). In conclusion, BFT achieves stable water quality, effective pathogen suppression, and enhanced production efficiency through microbial regulation, offering a viable water-saving, environmentally sound, and disease-resilient strategy for intensive P. vannamei culture.

Molecular Insights into Exoskeletal Remodeling: Transcriptomic Profiling of the Molting Cycle in the Red Swamp Crayfish Procambarus clarkii - Yunkuan Zhu; Yu Xu; Suwan Lu; Yuning Hu; Hui Xu; Jiajia Li; Hai Lin; Xuguang Li; Zhiqiang Xu (Fishes, 2026)
The molting of crustaceans is accompanied by exoskeleton reconstruction. To reveal the molecular regulation mechanism of exoskeleton remodeling, the transcriptomic profiles of the exoskeleton across the entire molting process in the red swamp crayfish Procambarus clarkii were investigated by RNA sequencing, yielding a total of 7671 differentially expressed genes (DEGs) across five different molting stages. Notably, the key DEGs were those related to cuticular exoskeleton synthesis (cuticular proteins), degradation (chitinase 2, chitinase 10) and hardening (chitin deacetylase 1), and their expression abundance varied by 10-fold or greater across the molting cycle. Analysis of Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that significantly enriched pathways included the structural constituents of the cuticle, structural molecule activity, chitin binding of chitin metabolism, and hormone biosynthesis. The expression profiles of nine selected molting-related DEGs were further validated via real-time RT-PCR assays. The acquired unique temporal expression patterns involved in exoskeleton remodeling provide a preliminary insight into the regulation of gene expression during the molting cycle in the red swamp crayfish.

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Spatial-socioeconomic semantic integration of remote sensing and urban planning maps for improved urban thermal environment characterization - Yu Kang; Zhe Zhang; Jiating Li; Zongying Zhao; Dongxue Li; Jiahua Yu; Jingjing Zhang; Xinjia Zhang; Qiao Hu; Yixue Chen; Jiajing Chen; Lin Li (Sustainable Cities and Society, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Effect of symmetry boundary simplification on coupled heat transfer of an sCO2-cooled immersed tube in a fluidized bed - Yu Huang; Jiahao Hu; Shanwei Hu; Lin Li; Xuetao Wang; Linfeng Miao; Lunbo Duan (Fuel, 2026)

Dynamic cross-linked/conductive dual-network polyurethane for integrated EMI shielding, thermal management and motion sensing - Sijie Yu; Taotao Qiang; Xiaoyong Dong; Congcong Lin; Xiaonan Ruan; Guannan Dong; Haiyang Hu; Fangfang Dong; Chen Mi; Tianlin Chen; Chen Zhang; Longfang Ren (Chemical Engineering Journal, 2026)

Design, synergistic mechanisms, and application of a MXene@CuS–CeO₂ photothermal–nanozyme multimodal antibacterial material in real water systems - Zihao Yu; Jialiang Lin; Yan Wang; Chunlu He; Yuan Shi; Yongyou Hu; Yunyun Jiang; Jianhua Cheng (Chemical Engineering Journal, 2026)

Corrigendum to “An oxidized dextran-composite self-healing coated magnesium scaffold reduces apoptosis to induce bone regeneration” [Carbohydrate Polymers 327 (2024) 121666] - Zewen Shi; Fang Yang; Yiwei Hu; Qian Pang; Lin Shi; Tianyu Du; Yuhao Cao; Baiyang Song; Xueqiang Yu; Zhaoxun Cao; Zhewei Ye; Chen Liu; et al. (Carbohydrate Polymers, 2026)

TEDD 2.0: an advanced temporal gene expression database enabled by in-silico functional analyses for developmental mechanism investigation - Chi Chun Chan; King Kin Lam; Lin Chen; Mingyang Yu; Jingwen Hu; Yujie Zhu; Yuting Zheng; Jia Zheng; Kwong Wai Choy; Zirui Dong (Science China Life Sciences, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Drier year exhibits amplified promoting effects of shrub encroachment on methane uptake in Tibetan alpine meadows - Lili Nan; Zelong Zhang; Dezhao Gan; Huinan Li; Dongsheng Yu; Zhenrong Lin; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; et al. (Agricultural and Forest Meteorology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Methyl group donor‑resolved isotopic diagnostics reveal mechanistic diversity in UV‑driven methylation of Hg(II) - Lin Yang; Kun Zhang; Maojun Yu; Shiyu Li; Deming Han; Ben Yu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

Adsorption-diffusion of trace organics in Baijiu on porous Fe2O3 - Qianxi Jiang; Manjiao Chen; Xinjun Hu; Weiqiang Zhou; Fan Zhao; Liangliang Xie; Haili Yang; Jinlong Yu; Zhoujun Lin; Caihong Shen (Journal of Food Engineering, 2026)

Porous carbon derived from molten salt thermal treatment of rice husk with ultrahigh adsorption capacity for tetracycline removal from solution: An experimental and theoretical study - Yongda Huang; Haojie Zhang; Hongyun Hu; Yang Ren; Zhong Lin; Shuaijie Yu; Jing He; Shuai Li; Sihua Xu; Hong Yao (Journal of Environmental Chemical Engineering, 2026)

Effect of oxygen-containing functional groups on selenium removal by the carbonaceous adsorbent from MSW incineration flue gas - Shuaijie Yu; Shuai Li; Hongyun Hu; Linxia Gao; Zhong Lin; Chan Zou; Lu Dong; Yongda Huang; Hong Yao (Fuel, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Salicylic acid as a pathway inducer for improved bioremediation of oil-polluted saline-alkali soils by chemotactic S. Stutzeri M3 - Lin Li; Xiaoying Yu; Mingjun Wang; Huaji Sun; Jingyi Zhu; Xuehan Wang; Shuiquan Chen; Shugang Hu (Bioresource Technology, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

Atmospheric Submicron Aerosols Over the Tibetan Plateau: A Review - Lin Liang; Wenhui Zhao; Xiaomin Chen; Weiwei Hu; Pengfei Yu; Shan Huang (Current Pollution Reports, 2026)

Evaluation of the thermal preference and thermal tolerance of large yellow croaker Larimichthys crocea fingerlings in recirculating aquaculture system (RAS) - Yu Liu; Minhai Liu; Jian Yang; Zihan Wang; Yaoyang Duan; Liyu Shan; Xiafei Zheng; Hengzhen Ye; Jingjie Hu; Zhihua Lin (Aquaculture, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Terminal-carboxyl-engineered 3D PLA nanochannels via ionic liquid templating for high osmotic energy conversion - Leqi Chang; Cuncai Lin; Xingteng Ma; Yuankun Ning; Zeyang Yu; Shuhong Hu; Yanshu Chen; Xin Sui; Longcheng Gao; Kunyan Sui (Chemical Engineering Journal, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Gasdermin D in Neurodegenerative Diseases: Pathogenic Roles and Therapeutic Perspectives - Jiaxin Zhou; Chaolin He; Jianqiao Li; Jianming Wu; Hong Lin; Anguo Wu; Xiaogang Zhou; Guangqiang Hu; Lu Yu (Molecular Neurobiology, 2026)

Inhibition of Neuroinflammation by Costunolide Attenuates Hypoxic-Ischemic Brain Damage via the PI3K/AKT Pathway in Neonatal Rats - Yingying Hu; Rengcheng Qian; Yifeng He; Qiqi Gao; Xun Wang; Huilin Lin; Wei Lin; Yu Fang; Jianghu Zhu; Xingyun Wang; Yan Nan; Zhenlang Lin (Molecular Neurobiology, 2026)

Coupled regulation mechanisms of carbon sequestration, microbial communities, and manganese stabilization in manganese-contaminated soil by phosphorus-modified biochar - Yuyan Deng; Yu Yang; Lin Tu; Yifan Liao; Anyu Li; Huiquan Zhai; Hua Deng; Yang Li; Lening Hu (Applied Soil Ecology, 2026)

CT-HiffNet: A contour-texture hierarchical feature fusion network for cropland field parcel extraction from high-resolution remote sensing images - Hao Wu; Junyang Xie; Weihao Deng; Anqi Lin; Abdul Rashid Mohamed Shariff; Shamshodbek Akmalov; Wenbin Wu; Zhaoliang Li; Qiangyi Yu; Qunming Wang; Jian Zhang; Xin Mei; et al. (Computers and Electronics in Agriculture, 2025)

An advanced approach for multiscale aboveground biomass estimation by integrating UAV, backpack LiDAR and high-resolution imageries: A case study in Liriodendron sino-americanum mixed forests - Yonglei Shi; Xin Shen; Miao Hu; Aihong Yang; Kai Zhou; Faxin Yu; Yang Tao; Lin Cao (Computers and Electronics in Agriculture, 2025)

Dihydroartemisinin targets ANXA2 to suppress hepatocellular carcinoma angiogenesis through the PI3K/AKT signaling pathway - Lulu Cao; Lihui Wang; Jun Lin; Jian Zhao; Bolun Xu; Jianxin Chen; Juanjuan Hu; Siwei Wang; Junhua Yu (Tissue and Cell, 2025)

Integrated physiological and metabolomic analysis reveals metabolite diversity and cultivar-specific characteristics during post-ripening in four Torreya grandis cultivars - Zhenmin Ma; Han Tao; Lin Li; Ruqi Meng; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Fei Gao; Mohamed A. Farag; Zuying Zhang; Jiasheng Wu; Lili Song (Postharvest Biology and Technology, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Grain size and geochemical evidence for the integration of the Yellow River through the Sanmen Gorge - Han Hu; Ziying Yu; Jiaxing Yang; Jiayi Lin; Wenjing Yang; Baofeng Li; Gang Hu; Xin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Oxygen vacancies in MnO2 as active sites for photothermal catalytic degradation of formaldehyde - Yu-Syuan Liou; Yu-Chun Liao; Yu Age; Masaaki Yoshida; Ke-Hsuan Wang; Van-Huy Nguyen; Kun-Yi Andrew Lin; Chechia Hu (Journal of Environmental Chemical Engineering, 2025)

Impact of KCl and L-Arg substitution on low salt beef patties: oxidative, textural, flavor, and microbial insights - Chuanlong Yu; Lingli Chen; Hui Chen; Suyun Lin; Wenbing Hu; Kehui Ouyang; Wenjun Wang (Food Chemistry, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Corrigendum to “Emerging risk of chronic microplastic exposure: Evolution of Escherichia coli toward antibiotic resistance and pathogenicity” [Chemical Engineering Journal 523 (2025) 168621] - Xi Li; Liusheng Lei; Jing Yu; Xiaowei Wu; Wenjin Hu; Huai Lin (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Tungsten-induced oxygen vacancy in MOF-derived MnO2@carbon for solar-driven photothermal oxidation of formaldehyde - Yu-Yi Lin; Wen-Ling Chen; Yuji Takaki; Yu-Syuan Liou; Masaaki Yoshida; Szu-Chia Chien; Lely Ayu Ningsih; Jiří Ščučka; Chechia Hu (Chemical Engineering Journal, 2025)

Structural characterization and immunomodulatory activity of a novel pectin polysaccharide extracted from Gardenia jasminoides fruit - Yue Guo; Yanan Cheng; Bing Zheng; Jianhua Xie; Yi Chen; Huasi Lin; Hui Liu; Xiaobo Hu; Qiang Yu (Carbohydrate Polymers, 2025)

Multiple Mechanisms and Therapeutic Strategies for the Involvement of AMPK in the Development of Alzheimer’s Disease - Lin Yu; Xue Yang; Hui-Ping Lei; Yue-Ting Hu; Ling-Nan Wu; Shao-Yu Zhou; Feng Jin (Molecular Neurobiology, 2025)

Statistical inferences of differences and correlations in the seismic frequencies of large-scale fault zones in Western Sichuan, China - Yuan Xue; Dan Hu; Junreng Ge; Xinyu Yao; Mingyue Dai; Bingyan Fan; Yu Ming; Muchen Lin (Journal of Seismology, 2025)

From immunosuppression to immune reprogramming: is triptolide a potential “immune reset” agent in autoimmune diseases? - Dehui Yu; Hu Lin (Immunologic Research, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

An advanced structure correction spectral model using UAV multispectral images and LiDAR-based crown boundaries for estimating crown leaf nitrogen concentration in subtropical Liriodendron sino-americanum plantation - Jie Li; Kai Zhou; Faxin Yu; Miao Hu; Lin Cao (Computers and Electronics in Agriculture, 2025)

Novel insights into quorum-sensing microbe combined with dimethylsulfoniopropionate enhancing bioremediation of oil-contaminated sediment under typical deep-sea conditions: The performances and molecular mechanisms - Shugang Hu; Shijie Li; Lingzhe Wang; Shuo Wang; Dongle Cheng; Jianliang Xue; Yu Gao; Siheng Lin; Chengbo Li; Yanlu Qiao; Yuyang Liu (Marine Pollution Bulletin, 2025)

Late Holocene extreme dust events in the arid Central Asia recorded by lake sediments in Tien Shan - Min Zheng; Xiaozhong Huang; Ning Wang; Menghan Qiu; Jun Zhang; Lixiong Xiang; Shaojun Chen; Muhammad Farqan; Ruiqi Min; Tao Wang; Chong Huang; Xiuxiu Ren; et al. (Quaternary Science Reviews, 2025)

Paleo-Asian Ocean subduction-related multiple mantle metasomatism: Constraints from in-situ Sr Mg isotopes of mantle xenoliths in the Xing-Meng orogenic belt - Xudao Liu; Kaizhang Yu; Yongsheng Liu; Zhicheng Liu; Chunfei Chen; Jie Lin; Ao Yang; Xi Zhu; Zhaochu Hu (Lithos, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Effects of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality, myofibrillar protein and ice crystal morphology of largemouth bass during air freezing - Junde Ren; Feifei Hu; Farooq Muhammad; Lihui Hu; Tao Song; Maninder Meenu; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Food Research International, 2025)

Structure-function modulation of sodium caseinate: Insights from non-covalent reuterin binding - Mao-Cheng Sun; Jie-Ting Wang; Ying-Di Wang; Lin-Yu Hu; Shi-Qi Yu; Tiehua Zhang; Changhui Zhao (Food Chemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Emerging risk of chronic microplastic exposure: Evolution of Escherichia coli toward antibiotic resistance and pathogenicity - Xi Li; Liusheng Lei; Jing Yu; Xiaowei Wu; Wenjin Hu; Huai Lin (Chemical Engineering Journal, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

In situ polyamide nanofiltration coatings for enhanced lithium extraction from high Mg/Li brines - Qiyue Fan; Jie Lin; Yue Sun; Xiangting Hu; Hang Yu; Zhenda Lu (Chemical Engineering Journal, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Unraveling phylogenetic conflicts and adaptive evolution in Chiroptera using large-scale mitogenomes and nuclear genes - Dengfeng Guan; Xin Huang; Guangping Huang; Jiang Zhou; Lin Yang; Wenhua Yu; Weijian Guo; Jiang Feng; Yi Wu; Yibo Hu; Fuwen Wei (Science China Life Sciences, 2025)

New relationship and mechanisms between Northeast China Cold Vortex and pre-flood season precipitation in South China under global warming - Baihui Guo; Yihe Fang; Yitong Lin; Yiqiu Yu; Chunyu Zhao; Yu Zhang; Yamin Hu; Mingsheng Wang (Climate Dynamics, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Investigation of transport and deposition behavior and mechanisms of micro-nano-bubbles in porous media - Yazhou Cao; Dantong Lin; Zhen-Yu Yin; Liming Hu (Journal of Hydrology, 2025)

Diapycnal fluxes of nutrients in the North Pacific Subtropical Gyre - Chuanjun Du; Minhan Dai; Zhiyu Liu; Zhendong Hu; Jin-Yu Terence Yang; Kuanbo Zhou; Hongyang Lin; Zhongwei Yuan; Lifang Wang; Tao Huang; Liguo Guo; Zhe Wang; et al. (Global and Planetary Change, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

PUFFER-DETR: Tiger puffer similar abnormal behavior recognition based on transformer - Yixi Zhang; Zeyuan Hu; Jihang Liu; Yinjia Li; Jianjian Lin; Yue Wang; Hong Yu (Aquacultural Engineering, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

A three-dimensional Pt@Ti₃C₂Tₓ-based smart platform for discrimination of hydrated ammonia in multi‐scenario environmental monitoring - Qingqing Zhou; Chencheng Hu; Yu Qi; Xiaoyi Tan; Jiaqi Yang; Zitong Kan; Long Yang; Biao Dong; Zhiyong Chang; Hongwei Song; Lin Xu (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Synergistic triboelectric and antibacterial properties in biodegradable nanofiber membranes for air filtration - Yi Liu; Shuai Zheng; Mengqi Wang; Xiaoyu Zhang; Fei Wang; Jun Yu; Xiaodong Hu; Jinyou Lin; Yuqing Liu (Journal of Hazardous Materials, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Membrane technology for microplastic removal: Microplastic occurrence, challenges, and innovations of process and materials - Zhuoran Lin; Xingyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Wei Yu; Bisheng Li; Leihong Zhao; Mingyi Ying (Chemical Engineering Journal, 2025)

IoT-enabled hierarchical thermoelectric nanocomposites for adaptive fire safety systems: Self-powered sensing and threshold-tunable alerts - Chuanshen Wang; Haorui Dun; Lu Liu; Hongliang Ding; Hongfei He; Bicheng Lin; Wenyu Hu; Na Sun; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Amino-enhanced MIL-101(Fe) piezocatalysis for in-situ hydrogen peroxide generation and selective production of 1O2 for organic pollutants degradation - Wenzhi Du; Xinyu Xu; Rumeng Yang; Yuxing Qiao; Yingying Yu; Lin Tao; Jiayue Hu; Yichao Huang; Mingshan Zhu (Chemical Engineering Journal, 2025)

Charge/conformation-transformable phosphopeptide@hollow covalent organic frameworks as molecular gates for electrochemical analysis - Lin Wang; Minghui Wang; Gaoxiang Wang; Haojie Xie; Yu Hang; Dongmei Zhang; Sha Zhu; Xiafei Hu; Genxi Li (Chemical Engineering Journal, 2025)

Climate change aggravates the Spatiotemporal imbalance of water resources in the Rice-Wheat rotation region of the middle and lower Yangtze river - Hao He; Man Li; Lin Zhao; Jinge Yu; Qi Li; Zhenghua Hu; Xuesong Zhang (Theoretical and Applied Climatology, 2025)

Plasma-Derived Small Extracellular Vesicles miR- 182 - 5p Is a Potential Biomarker for Diagnosing Major Depressive Disorder - Lin-Lin Zhu; Lian-Di Li; Xuan-Yu Lin; Jian Hu; Chun Wang; Yi-Jun Wang; Qi-Gang Zhou; Jing Zhang (Molecular Neurobiology, 2025)

Butenolide synergises with vancomycin to eradicate pre-formed biofilm of Staphylococcus aureus by interfering with energy-associated metabolism - Dai-Xin Hu; Jinyou Liang; Jing Yan; Zhi-Wen Ma; Hai-Lin Li; Ying Xu; Yu Zhang; Qi Yin (Biofouling, 2025)

Two new chemical constituents from the aerial parts of Tripterygium wilfordii - Xia Zhang; Lei Huang; Yu-Jun Tang; Ya-Lin Hu; Wei Xu; Hong-Yu Li; Yu-Bo Zhang; Xiao-Qi Zhang; Guang-Xiong Zhou (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A PLA2-responsive nanoagonist to boost immunotherapy via targeted release of lipid mediators in cold tumor microenvironment - Hui-Ping Wen; Meng-Die Zhu; Di Ning; Zhi-Gang Wang; Yusi Hu; Chuan-Ming Yu; Dai-Wen Pang; Shu-Lin Liu (Science Bulletin, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Distribution of and associations between ARGs and pathogenic bacteria in soils affected by heavy metal contamination in mining areas - Yanbin Du; Yijia Liu; Caihong Yu; Xuesong Hu; Suya Ma; Jiacheng Zou; Ronghua Lin; Yanhua Hou; Menglun Wang; Nan Zhang (Journal of Environmental Chemical Engineering, 2025)

Updated insights into steady-modified anthocyanin food packaging: Novel strategies, characterization, application and future challenges - Jia-Yin Huang; Yu-Lei Chen; Duan-Quan Lin; Le-Chang Sun; Kang Liu; Ling-Jing Zhang; Ya-Qin Hu; Min-Jie Cao (Food Chemistry, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Associations of Metal Mixtures with Lipid Profiles: Exploring the Mediating Role of Testosterone in a Cross-Sectional Study - Sencai Lin; Ying Yang; Junxiu He; Sihan Hu; Yu Bao; Xiaoting Ge; Xiaobo Yang (Biological Trace Element Research, 2025)

Identification of gut microbiota causally associated with aging and longevity and mediation roles of the cerebrospinal fluid proteins: proteomic genetic evidence from Mendelian randomization - Ruonan Liu; Zheng Zhu; Yuanyue Zhu; Xin Lin; Hongjie Li; Tiange Wang; Jie Zheng; Mian Li; Zhiyun Zhao; Yu Xu; Jieli Lu; Weiqing Wang; et al. (GeroScience, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Amino-functionalized MIL-101(Fe)-NH2 as efficient peracetic acid activator for selective contaminant degradation: Unraveling the role of electron-donating ligands in Fe(IV) generation - Renjie Pan; Zongchen Li; Tian-Yang Zhang; Qi Fu; Zheng-Xiong Zheng; Jun Shi; Jian Lu; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Journal of Hazardous Materials, 2025)

Tetraphenylethene-based covalent organic polymers with tunable Electrochemiluminescence for ultrasensitive detection of tetracycline - Ziqi Lian; Zhoumei Lin; Yu Wang; Li Tan; Wenjing Gao; Yuchan Liu; Huizhen Ma; Junqiang Luo; Chenyao Chen; Wanzhen Chen; Rongkai Ye; Ying Ma; et al. (Food Chemistry, 2025)

Unveiling a new hemocyte subpopulation in white shrimp (Penaeus vannamei) and the characterization of immune response in hemocyte subpopulation - Novi Rosmala Dewi; Ari Widodo; Muhammad Ar Rozzaaq Nugraha; Min-Da Yang; Ta-Jeng Yang; Yu-Ru Lin; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Enhancement of methane production from pig manure by ferrate pretreated anaerobic digestion: Performance and mechanism - Yukai Zheng; Jiarui Wang; Xiaojun Niu; Xintai Su; Xiaoyan He; Yunxia Hu; Dongmei Zhao; Deye Chen; Yu Lin; Kai Li (Chemical Engineering Journal, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Decoding the nexus of surface water and groundwater in Northwestern China: Insights from long-term irrigation activities and numerical modeling - Lin Gan; Litang Hu; Zhongjing Wang; Na Zhang; Guiyu Yang; Suyue Yu (Journal of Hydrology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Unveiling high-light-use efficiency in Juglans mandshurica: Adaptive insights from leaf morphology and physiology - Qinhui Zhang; Dan Peng; Xiaona Pei; Yitong Chen; Zihan Yan; Mingrui Kang; Jinrong Hu; Yulu Pan; Jingxin Yu; Lu Xu; Huicong Lin; Xiyang Zhao (Forest Ecology and Management, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Enhancing oil/water emulsion separation with inkjet printed beetle-inspired zeolitic imidazolate framework-67 modified membranes - Xinyu Hu; Hongli Xie; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin; Leihong Zhao; Genying Yu (Desalination, 2025)

Corrigendum to “Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils” [Biomass & Bioenergy 197 (2025) 107823] - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

Phosphorus-modified biochar regulates CO2 emissions and bacterial communities in an incubation study of manganese-contaminated soils - Yu Yang; Lin Tu; Yifan Liao; Dong Zhao; Shunyun Ye; Haiping Luo; Anyu Li; Hua Deng; Lening Hu (Biomass and Bioenergy, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Melatonin attenuates inflammatory bone loss by alleviating mitophagy and lactate production - Zexin Lin; Yuan Gu; Yingsong Liu; Zilin Chen; Shuai Fang; Zhuan Wang; Zixian Liu; Qingrong Lin; Yanjun Hu; Nan Jiang; Bin Yu; Guanqiao Liu (Apoptosis, 2025)

Novel impact of metal ion-induced cell death on diabetic cardiomyopathy pathogenesis and therapy - Jingjing Jiang; Shengnan Hu; Kaibo Hu; Leyang Xiao; Jitao Lin; Yixuan Chen; Deju Zhang; Yangliu Ou; Jing Zhang; Linhui Yuan; Wenting Wang; Peng Yu (Apoptosis, 2025)

Single-cell RNA sequencing reveals the heterogeneity of hepatopancreas cells and their association with gonadal development in the red swamp crayfish Procambarus clarkii - Lin Du; Yuning Hu; Siyu Lu; Xuguang Li; Jiajia Li; Hai Lin; Jiaxin Yang; Yu Xu; Zhiqiang Xu (Aquaculture, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Research on ship dynamic feature extraction and prediction method based on visual data - Siling Lin; Yong Li; Yu Hu; Jia Shi; Shaohua Wang; Peng Wang; Qiang Mei; Xiao Li; Haowen Wei (Ocean Engineering, 2025)

Polystyrene microplastics attenuated the impact of perfluorobutanoic acid on Chlorella sorokiniana: Hetero-aggregation, bioavailability, physiology, and transcriptomics - Zhilin Zhao; Xiaoying Zheng; Yue Li; Zongshuo Han; Yu Tang; Tianxing Hu; Tao Lin (Journal of Hazardous Materials, 2025)

Effective SSR markers for assessing population structure, genetic diversity, and volatile compounds in Atractylodis Rhizoma - Haotian Zhong; Lina Chen; Lei Chen; Xiao Huang; Ling Gong; Juan Hu; Yuling Zeng; Kun Yu; Lin Sen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Characterizing and decoding the dynamic alterations of volatile organic compounds and non-volatile metabolites of dark tea by solid-state fermentation with Penicillium polonicum based on GC–MS, GC-IMS, HPLC, E-nose and E-tongue - Xilu Zhang; Xingjun Lu; Cheng He; Yulian Chen; Yuanliang Wang; Lin Hu; Qing Qing; Mingzhi Zhu; Zhonghua Liu; Yu Xiao (Food Research International, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Demonstration of a kW-scale flexible multi-fuel reforming power generation system for decentralized energy supply - Zaixing Wang; Yi Lin; Yu Guo; Fengli Liang; Zhenzong He; Jiajun Hu; Junkui Mao; Molly Meng-Jung Li (Chemical Engineering Journal, 2025)

Towards Sustainable High-Performance Materials: Tailoring the Mechanical Properties of Bamboo-Based Fiber Composites through Controlled Processing - Juan Hu; Shaodi Zhang; Jian Lin; Yanglun Yu; Wenji Yu; Yuxiang Huang (Chemical Engineering Journal, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Reprocessable bio-based rubber with hierarchical hydrogen bonding: A sustainable solution for high strength, superior extensibility, and recyclability - Wei-Chen Zhou; Xue-Qin Gao; Jia-Hao Li; Gui-Lin Hu; Yu-Zhong Wang; Cong Deng (Chemical Engineering Journal, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Ferrihydrite enhance performance in anaerobic digestion of pig manure: Methane production, Feammox and metabolic pathway - Yukai Zheng; Jiarui Wang; Xiaojun Niu; Xintai Su; Xiaoyan He; Yunxia Hu; Dongmei Zhao; Deye Chen; Yu Lin; Kai Li (Journal of Water Process Engineering, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

FengYun-3 meteorological satellites’ microwave radiation Imagers enhance land surface temperature measurements across the diurnal cycle - Yuyang Xiong; Tianjie Zhao; Haishen Lü; Zhiqing Peng; Jingyao Zheng; Yu Bai; Panpan Yao; Peng Guo; Peilin Song; Zushuai Wei; Ronghan Xu; Shengli Wu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Iron-carbon amendment enhanced pollutant removal and greenhouse gas reduction in constructed wetlands under PFBA stress - Jiaqing Tao; Xiaoying Zheng; Chao Zhou; Zhilin Zhao; Tianxing Hu; Yi Fan; Yu Tang; Rui Wang; Tao Lin (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Temporal trend of organic carbon in the East Siberian Arctic shelf sediments and its relation to the recent climate forcing - Jialong Luo; Li Jiang; Limin Hu; Zenghui Yu; Weini Chong; Fudong Lin; Fenghua Su; Yanguang Liu; Kirill Aksentov; Alexander Bosin; Anatolii Astakhov; Xuefa Shi (Acta Oceanologica Sinica, 2025)

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

Loss of KIFC1 activity induces spindle instability and actin defects during porcine oocyte maturation - Yu-Ran Wang; Peng-Jie Wang; Le-Yan Tao; Lin-Lin Hu; Qiang-Qiang Liu; Shao-Chen Sun; Jing-Xi Wei; Yue Wang (Theriogenology, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

CAR-NK cell therapy: a potential antiviral platform - Ming-Hao Lin; Li-Juan Hu; Jeffrey S. Miller; Xiao-Jun Huang; Xiang-Yu Zhao (Science Bulletin, 2025)

Chronological and palaeoecological insights into the Dayakou fauna in Yanjinggou, Chongqing, China: Responses of large mammals to the Early-Middle Pleistocene Climate Transition - Haiqian Hu; Haowen Tong; Fei Han; Hui Dai; Wanbo Huang; Qigao Jiangzuo; Paul Rummy; Xunqian Wang; Yu Lin; Guangbiao Wei (Quaternary Science Reviews, 2025)

Advanced sequential treatment approach for enhanced recovery in tungsten-nickel electroplating wastewater - Shilong Lin; Bingzhi Yi; Xiangjun Hu; Linna Fang; Shuiyong Yu; Sanchuan Yu; Doufeng Wu (Journal of Water Process Engineering, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Impacts of an environmental ototoxic pollutant on fish fighting behaviors - Jiun-Lin Horng; Yu-Huan Hu; Hsi Chen; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Mobile measurements of atmospheric decamethylcyclopentasiloxane (D5) in Eastern China - Haifeng Yu; Yunhua Chang; Lin Cheng; Wen Tan; Liang Zhu; Jianlin Hu (Atmospheric Environment, 2025)

Arsenic and its associated metabolism genes in Chinese soils: a comprehensive investigation of mine and paddy soils - Yu-Ting Lin; Rui-Lian Yu; Gong-Ren Hu; Jing-Wei Sun; Yu Yan (Journal of Soils and Sediments, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Effective denitrification from landfill leachate using magnetic PVA/CMC/DE carrier immobilized microorganisms - Yunshuang Hu; Yufei Gu; Jiahui Tan; Chong Ding; Xinyi Yu; Zhixia Li; Hongfei Lin (Waste Management, 2025)

Urbanization induced Urban Canopy Parameters enhance the heatwave intensity: A case study of Beijing - Tuo Chen; Shirao Liu; Xuecao Li; Lin Pei; Mengqing Geng; Guojiang Yu; Zitong Shi; Tengyun Hu (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Integration of manganese ores with activated carbon into constructed wetland for greenhouse gas emissions reduction - Yu Huang; Xiaoying Zheng; Zhilin Zhao; Jiaqing Tao; Tianxing Hu; Zongshuo Han; Tao Lin (Journal of Environmental Management, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

A New Rock Damage Constitutive Model Based on Usher Function and its Application to Brittleness Evaluation - Yun-peng Guo; Dong-qiao Liu; Sheng-kai Yang; Yang Wang; Yi Hu; Xiao-peng Zhang; Jie-yu Li; Yan-peng Lin; Zhong-wei Li (Rock Mechanics and Rock Engineering, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Insomnia in Parkinson’s Disease: Causes, Consequences, and Therapeutic Approaches - Xiaoyu Duan; Hanshu Liu; Xinyu Hu; Qinwei Yu; Guiying Kuang; Long Liu; Shurui Zhang; Xinyi Wang; Jingwen Li; Danfang Yu; Jinsha Huang; Tao Wang; et al. (Molecular Neurobiology, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Structural characterization, HepG2 cell cytoprotective ability, and antioxidant mechanism of novel antioxidant peptides identified from black soldier fly larvae (Hermetia illucens L.) - Leying Meng; Dandan Yu; Jianan Lin; Yongmei Hu; Nan Peng; Shumiao Zhao (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

Preparation of nanocellulose-silk fibroin stiff hydrogel and high absorbing-low expansion xerogel via polysaccharide-protein interactions - Yue Ma; Tian Huang; Zhixing Hu; Juan Yu; Liang Liu; Lin Lin; Meijuan Chen; Ruoxian Jia; Xin Li; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2025)

Mitigation of cadmium and arsenic in rice grain by zero valent iron through modifying the soil chemical property and microbial community structure - Tingting Li; Dasong Lin; Chao Liu; Junhui Zhang; Yuefeng Yu; Fuhai Zheng; Junming Hu (Plant and Soil, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Microneedle patch with pure drug tips for delivery of liraglutide: pharmacokinetics in rats and minipigs - Hongbing Lin; Jinbin Liu; Yulin Hou; Zhiyan Yu; Juan Hong; Jianghong Yu; Yu Chen; Jingwen Hu; Dengning Xia (Drug Delivery and Translational Research, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Detection of Tetracycline in Farm Wastewater by Nitrogen-doped Carbon Quantum Dots - Peilan Yu; Lintong Ji; Teng Wang; Juan Hu; Lihao Jiang; Shancai Guo; Yongjian Pan; Jianyuan Lin (Journal of Fluorescence, 2024)

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Sulforaphane acts through the NFE2L2/AMPK signaling pathway to protect boar spermatozoa from cryoinjury by activating antioxidant defenses - Guangzhi Zhang; Fei Wen; Yu Li; Pingyu Sun; Yang Li; Zhangtao Hu; Hui Wang; Yunhui Ma; Guodong Liang; Lin Chen; Ke Yang; Jianhong Hu (Theriogenology, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

The improvement of gel properties and volatiles for frozen egg white melted assisted with ultrasound - Xiaole Xiang; Shiqin Dong; Le Chen; Yongle Liu; Yingqun Wu; Meijuan Yu; Gan Hu; Shugang Li; Lin Ye (Food Research International, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Genome-Based Classification of ‘Haloarcula aidinensis’ and Description of Three Novel Halophilic Archaea Isolated from an Inland Saline Lake, Coastal Saline Soil, and a Marine Solar Saltern - Xue Ma; Yao Hu; Jing Hou; Yu-Guang Zhou; Heng-Lin Cui (Current Microbiology, 2024)

Folding of a single layer in an anisotropic viscous matrix under layer-parallel shortening - Yuan-bang Hu; Paul D. Bons; Tamara de Riese; Shu-gen Liu; Maria-Gema Llorens; Eloi González-Esvertit; Enrique Gomez-Rivas; Dian Li; Yu-zhen Fu; Xue-lin Cai (Journal of Structural Geology, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

Nutrient-rich sediment promotes, while fertile water inhibits the growth of the submerged macrophyte Vallisneria denseserrulata: implications for shallow lake restoration - Haodong Chen; Liu Yang; Zhenmei Lin; Sipeng Yao; Hu He; Xiaolong Huang; Zhengwen Liu; Erik Jeppesen; Jinlei Yu (Hydrobiologia, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Nrf2 affects DNA damage repair and cell apoptosis through regulating HR and the intrinsic Caspase-dependent apoptosis pathway in TK6 cells exposed to hydroquinone - Lin Chen; Pu Guo; Lu Zhai; Lingxue Yu; Delong Zhu; Xiaoyi Hu; Zhuanzhuan Li; Yuting Chen; Qian Sun; Lei Sun; Hao Luo; Huanwen Tang (Toxicology in Vitro, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ore-forming material sources of the Pakbeng gold deposit, Laos: Evidence from fluid inclusions, H-O-S isotopes, and trace elements - Hong Liu; Shuyi Dong; Yinglei Liu; Xiaoyu Lin; Yuhan Liu; Hu Wang; Yu Zhao; Jie Zhang; Xuexing Xie (Ore and Energy Resource Geology, 2024)

Combined effects of thermal environment and gene regulation on metabolic enzyme activities of major metabolic tissues in a winter-breeding amphibian - Chi-Ying Zhang; Hua-Li Hu; Yu Wang; Lin Zhang; Guo-Hua Ding (Journal of Thermal Biology, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

Can stable carbon isotope fingerprints be competent for geographic traceability of rice? - Yu Liu; Jingwen Hu; Guoguang Wang; Huanyu Yang; Lin Hong; Jing Xu; Haixia Wang (Food Chemistry, 2024)

Effects of the Lactobacillus fermentation on Dendrobium officinale polysaccharide: Structural, physicochemical properties and in vitro bioactivities - Huasi Lin; Yanan Cheng; Lanxi Liang; Xiaoting Qin; Xuewen Dong; Yue Guo; Qiang Yu; Guowen Zhang; Xiaobo Hu (Food Bioscience, 2024)

Selenium-enriched Bifidobacterium longum DD98 significantly improves the efficacy of Mesalazine and Cyclosporin A in colitis mice - Yongjia Hu; Chengchen Xu; Ziqi Xu; Xuan Chen; Fei Gao; Ting Lin; Ping Yang; Shidong Kan; Yu Yin; Daijie Chen (Food Bioscience, 2024)

Plantago asiatica seed as a protective agent for mitigating metals toxicity on Penaeus vannamei - Zhen-Hao Liao; Yeh-Fang Hu; Wen-Shao Wu; Huu-The Nguyen; Sofia Priyadarsani Das; Huai-Ting Huang; Yu-Ru Lin; Po-Tsang Lee; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Numerical study of energy consumption in spacer-filled feed channels through 3D inverse modeling and computational fluid dynamics - Hui Guan; Jiacheng Li; Doufeng Wu; Sanchuan Yu; Peifeng Lin; Xiao Hu (Desalination, 2024)

High entropy catalysts in electrolytic water splitting: A review from properties to applications - Zhi-Jie Zhang; Ning Yu; Yi-Lin Dong; Guanqun Han; Han Hu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Sodium disilicate pretreatment enhancing methane production from anaerobic digestion of waste activated sludge - Yu Zhang; Shushan Hu; Jinze Li; Miao Liu; Linji Xu; Lin Li; Qiang He; Li Gu (Chemical Engineering Journal, 2024)

Distribution characteristics, sources and risk assessment of heavy metals in the surface sediments from the largest tributary of the Lancang River in the Tibet Plateau, China - Min Liu; Liangyuan Zhao; Li Lin; Yuting Zhang; Huawei Huang; Wei Deng; Yunjiao He; Jingxiang Tao; Yuan Hu; Luyi Nan; Yu Xuan Zhu (Environmental Geochemistry and Health, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Application of Multiple Geophysical Exploration Methods in the Exploration of Marine Sand Resources in the Northern Offshore Waters of the South China Sea - Gang Yu; Xichong Hu; Jie Fang; Ying Yang; Yongcong Zhang; Jinhui Lin; Jingyi Liu; Libing Qian (Journal of Marine Science and Engineering, 2024)
Marine sand, in addition to oil and gas resources, is the second-largest marine mineral resource. The rational development and utilization of marine sand resources are conducive to the growth of the marine economy. In the process of marketing marine sand in China, local authorities are required to delineate auctioned sand mining areas after a general survey, commonly referred to as preliminary exploration. Marine sand can be categorized into surface marine sand and buried marine sand. Buried marine sand deposits are buried beneath the sea floor, making it challenging to locate them due to their thin thickness. Consequently, there exist numerous technical difficulties associated with marine sand exploration. We conducted the preliminary research work in the waters off Guangdong Province of the South China Sea, employing a reduced drilling and identifying a potentially extensive deposit of marine sand ore. In this study, various geophysical methods such as sub-bottom profile survey, single-channel seismic survey, and drilling engineering were employed in the northern offshore waters of the South China Sea. As a result, two distinct marine sand bodies were delineated within the study area. Additionally, five reflective interfaces (R1, R2, R3, R4, and R5) were identified from top to bottom. These interfaces can be divided into five seismic sequences: A1, B1, C1, D1, and E1, respectively. Three sets of strata were recognized: the Holocene Marine facies sediment layer (Q4m), the Pleistocene alluvial and pluvial facies sediment layer (Q3al+pl), as well as the Pleistocene Marine facies sedimentary layer (Q3m). In total, two placers containing marine sand have been discovered during this study. We estimated the volume of marine sand and achieved highly favorable results of the concept that we are proposing a geologic exploration approach that does not involve any previous outcropping analogue study.

Dynamic migration and risk of cephalosporin antibiotic resistance genes: Move from pharmaceutical plants through wastewater treatment plants to coastal tidal flats sediments - Chifei Dong; Zishu Liu; Lin Zhu; Baofeng Zhang; Taolve Chi; Zhendi Yu; Meng Zhou; Lingtao Sun; Yuxiang Zhao; Lizhong Zhu; Baolan Hu (Water Research, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Insights into the impact of metals in waste activated sludge on its anaerobic digestion: From perspectives of physical structure and organic matter composition - Yu Zhang; Shushan Hu; Jinze Li; Yifei Wang; Miao Liu; Haoyang Li; Lin Li; Li Gu; Weiliang Pan; Qiang He (Fuel, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

Atomically precise gold nanoclusters as ROS-scavenging clusterzymes to treat high-fat diet-induced obesity - Jialuo Ding; Mengyuan Zhao; Yeying Li; Kexin Zhang; Hanxing Chen; Xinying Hu; Le Li; Yu Su; Xun Yuan; Zhenkun Lin (Chemical Engineering Journal, 2024)

Three-dimensional mixed-valence polyoxovanadates@polyaniline architecture towards high-performance rechargeable aqueous zinc-ion batteries cathode - Xue-Wei Liang; Yu-Ying Yang; Wen-Fei Di; Si-Yu Chen; Rui Zhang; Jisong Hu; Dunmin Lin; Yu Huo (Chemical Engineering Journal, 2024)

Effects of disposable face mask microplastics on soil properties and microbial communities - Liping Lin; Gongren Hu; Yangzi Lijin; Luowei Gan; Ruiqi Zhang; Ling Wang; Changhao Lu; Jianping Gao; Jiatai Lin; Le Yang; Yu Yan; Ruilian Yu (CATENA, 2024)

Slope displacement prediction based on multisource domain transfer learning for insufficient sample data - Hai-Qing Zheng; Lin-Ni Hu; Xiao-Yun Sun; Yu Zhang; Shen-Yi Jin (Applied Geophysics, 2024)

A SHAP machine learning-based study of factors influencing urban residents' electricity consumption - evidence from chinese provincial data - Yuanping Wang; Lang Hu; Lingchun Hou; Lin Wang; Juntao Chen; Yu He; Xinyue Su (Environment, Development and Sustainability, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

Sedimentary record of water-sediment regulation and channel shifts in the Yellow River (Huanghe) Delta - Shuqing Qiao; Xuefa Shi; Jianbu Wang; Lin Zhou; Yonggui Yu; Naishuang Bi; Limin Hu; Gang Yang; Zhengquan Yao (Marine Geology, 2024)

High-performance elimination of Cr(VI) in actual wastewater with a novel nZVI-based composite anchoring onto amino-grafted chitosan - Lixin Huang; Junqi Wei; Haiying Lin; Bin Xue; Yu Duan; Mingzhi Li; Zixuan Chen; Jiatong Lv; Lianghong Li; Xianghua Wu; Qiuyan Hu (Journal of Water Process Engineering, 2024)

Antimicrobial effect of plasma-activated water combined with tartaric acid against Staphylococcus aureus and its application on fresh-cut asparagus lettuce - Wei Wu; Jing Zhang; Tangjun Li; Zhenyang Hu; Shuting Huang; Mengshi Lin; Yunfei Xie; Zhilong Yu (Food Bioscience, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

Effects of Taiwanese indigenous cinnamon (Cinnamomum osmophloeum) leaf hot-water extract on nonspecific immune responses, resistance against Vibrio parahaemolyticus, nonviable cells, and haemocyte subpopulations in white shrimp (Penaeus vannamei) - Muhammad Ar Rozzaaq Nugraha; Yu-Ru Lin; Novi Rosmala Dewi; Huai-Ting Huang; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

In-situ electrochemical study on the effects of Fe(III) on kinetics of pyrite acidic pressure oxidation - Yu Zhang; Can Cui; Sen Lin; Heping Li; Lian Yang; Yadian Xie; Hailiang Hu; Lingyun Zhou; Huanjiang Wang; Chunyan Li (Acta Geochimica, 2024)

Fungal composition associated with host tree identity mediates nutrient addition effects on wood microbial respiration - Zhenhong Hu; Marcos Fernández‐Martínez; Qinsi He; Zhiyuan Xu; Lin Jiang; Guiyao Zhou; Ji Chen; Ming Nie; Qiang Yu; Hao Feng; Zhiqun Huang; Sean T. Michaletz (Ecology, 2024)
Fungi are key decomposers of deadwood, but the impact of anthropogenic changes in nutrients and temperature on fungal community and its consequences for wood microbial respiration are not well understood. Here, we examined how nitrogen and phosphorus additions (field experiment) and warming (laboratory experiment) together influence fungal composition and microbial respiration from decomposing wood of angiosperms and gymnosperms in a subtropical forest. Nutrient additions significantly increased wood microbial respiration via fungal composition, but effects varied with nutrient types and taxonomic groups. Specifically, phosphorus addition significantly increased wood microbial respiration (65%) through decreased acid phosphatase activity and increased abundance of fast‐decaying fungi (e.g., white rot), while nitrogen addition marginally increased it (30%). Phosphorus addition caused a greater increase in microbial respiration in gymnosperms than in angiosperms (83.3% vs. 46.9%), which was associated with an increase in Basidiomycota:Ascomycota operational taxonomic unit abundance in gymnosperms but a decrease in angiosperms. The temperature dependencies of microbial respiration were remarkably constant across nutrient levels, consistent with metabolic scaling theory hypotheses. This is because there was no significant interaction between temperature and wood phosphorus availability or fungal composition, or the interaction among the three factors. Our results highlight the key role of tree identity in regulating nutrient response of wood microbial respiration through controlling fungal composition. Given that the range of angiosperm species may expand under climate warming and forest management, our data suggest that expansion will decrease nutrient effects on forest carbon cycling in forests previously dominated by gymnosperm species.

Effect of Dietary β-Glucan on Growth Performance, Antioxidant Responses, and Immunological Parameters of Coral Trout (Plectropomus leopardus) - Xiaoqi Hao; Ziyang Lin; Zhenhua Ma; Yukai Yang; Chuanpeng Zhou; Jing Hu; Wei Yu; Heizhao Lin (Fishes, 2024)
Although β-glucan has diverse benefits for fish health, the potential adverse impacts of excessive supplementation are poorly understood. This study investigated the optimal dosage of β-glucan for coral trout and explored the adverse effects of excessive supplementation. The results revealed that moderate β-glucan supplementation (1) significantly enhanced the weight gain rate and specific growth rate (SGR); (2) significantly improved the intestinal villus length (0.10%), muscle thickness (0.05–0.15%), and α-amylase and chymotrypsin activities (0.05–0.15%); (3) significantly increased liver catalase (CAT), glutathione reductase (GR), alkaline phosphatase, complement 3, immunoglobulin M (IgM), lysozyme, serum superoxide dismutase, CAT, glutathione peroxidase, GR, total antioxidant capacity, acid phosphatase, complement 4, and IgM activities and significantly reduced malondialdehyde contents; (4) upregulated genes in the liver associated with copper-zinc superoxide dismutase (SOD-1), manganese superoxide dismutase (SOD-2), CAT, GSH-Px1a, ACP6, AKP, LZ-c, IgM, C3, and C4-b. However, 0.20% β-glucan significantly inhibited the growth performance of coral trout compared with 0.10% β-glucan. Thus, 0.10% β-glucan represents the optimal dosage for promoting growth, antioxidant activity, and immune responses in coral trout, while higher β-glucan levels weakened these beneficial effects. With an SGR established by a cubic regression analysis, the optimal level of β-glucan for maximal growth of coral trout is 0.082%. This study provides new insights into the health impacts of β-glucan on fish.

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Two new aryltetralin-type lignans from Camellia oleifera husk - Huai-yu Cheng; Tian-qi Xu; Ya-lin Hu; Qing Shu; Wei Xu; Chun-lin Fan; Guang-xiong Zhou (Natural Product Research, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

Combined dilute alkali and milling process enhances the functionality and gut microbiota fermentability of insoluble corn fiber - Qing Jin; Yiming Feng; Xavier Cabana-Puig; Tran N. Chau; Ronnie Difulvio; Dajun Yu; Anyang Hu; Song Li; Xin M. Luo; Jactone Ogejo; Feng Lin; Haibo Huang (Food Chemistry, 2024)

Development of validated sandwich ELISA for detecting peanut allergen Ara h 3 in food - Jia-Fong Lin; Kee-Lung Chang; Bau-Shan Hsieh; Yu-Chen Hu; Edward S. Huang; Hsu-Sheng Yu (Food Chemistry, 2024)

An algorithm for modelling escalator fixed loss energy for PHM and sustainable energy usage - Xuwen Hu; Jiaqi Qiu; Yu Lin; Inez Maria Zwetsloot; William Ka Fai Lee; Edmond Yin San Yeung; Colman Yiu Wah Yeung; Chris Chun Long Wong (Energy and Buildings, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

The role of gut microbiota in mediating increased toxicity of nano-sized polystyrene compared to micro-sized polystyrene in mice - Huai Lin; Xin Li; Huihui Gao; Wenjin Hu; Shenbo Yu; Xi Li; Liusheng Lei; Fengxia Yang (Chemosphere, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Differential effects of oxytetracycline on detoxification and antioxidant defense in the hepatopancreas and intestine of Chinese mitten crab under cadmium stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Zhang; Hui Zhang; Zi-Ming Liu; Min-Hui Yu; Bing Hu (Science of The Total Environment, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Berberine hydrochloride delays citrus sour rot mainly by disrupting carbohydrate and energy metabolism of Geotrichum citri-aurantii spores - Lu Li; Bo Lin; Yu Ting; Maohui Li; Jinjin Hu; Jingjing Song; Yingjuan Yan; Jiaxin Chen; Hong Xiao; Nengguo Tao (Pesticide Biochemistry and Physiology, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

First record of the late Famennian conodonts in Qamdo, Tibet and their biostratigraphic implications - Yu-Ze Huang; Wen Guo; Wei Lin; Ping-Cuo Zhaxi; Le Yao; Ke-Yi Hu; Qiu-Lai Wang; Yu-Ping Qi (Palaeoworld, 2024)

Evidences for the influence from key chemical structures of per- and polyfluoroalkyl substances on their environmental behaviors - Yiru Zhuang; Jing Wu; Bingqi Dong; Fan Wang; Dongmei Hu; Yueling Zhang; Yu Bo; Lin Peng (Journal of Hazardous Materials, 2024)

Experimental investigation on the flow boiling of R134a in a plate heat exchanger with mini-wavy corrugations - Wei-chao Lao; Yi-dong Fang; Qing-hu Chen; Lin-jie Xu; Hui-nan Yang; Yu-qi Huang (International Journal of Refrigeration, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

Numerical seismic performance assessment and fragility analysis for gravity-type wharves considering the influence of soil liquefaction - Yung-Yen Ko; Ho-Hsiung Yang; Chi-Wen Hu; Yan-Jhih Huang; Yu-Ying Lin (Soil Dynamics and Earthquake Engineering, 2024)

Rh/InGaN1−O nanoarchitecture for light-driven methane reforming with carbon dioxide toward syngas - Yixin Li; Jinglin Li; Tianqi Yu; Liang Qiu; Syed M. Najib Hasan; Lin Yao; Hu Pan; Shamsul Arafin; Sharif Md. Sadaf; Lei Zhu; Baowen Zhou (Science Bulletin, 2024)

Landscape and risk assessment of microplastic contamination in farmed oysters and seawater along the coastline of China - Huai Lin; Xin Li; Wenjin Hu; Shenbo Yu; Xi Li; Liusheng Lei; Fengxia Yang; Yi Luo (Journal of Hazardous Materials, 2024)

Spatial distribution characteristics of carbazole and polyhalogenated carbazoles in water column and sediments in the open Western Pacific Ocean - Songtao Hu; Lijia Jiang; Lingbo Jiang; Leiming Tang; Anura Upasanta Kumara Wickrama Arachchige; Hao Yu; Zhaochao Deng; Longyu Li; Chunsheng Wang; Dongsheng Zhang; Chunlei Chen; Shiquan Lin; et al. (Journal of Hazardous Materials, 2024)

Optimization of ultrasonic extraction of bioactive components from Alpiniae oxyphyllae Fructus using response surface methodology - Yuyi Liu; Ruimin Wang; Xuan Hu; Chengfeng Yu; Zexin Wang; Lin Zhang; Sixin Liu; Congfa Li (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Bio-based and fireproof radiative cooling aerogel film: Achieving higher sustainability and safety - Wei Cai; Bicheng Lin; Liangyuan Qi; Tianyang Cui; Zhaoxin Li; Junling Wang; Sicheng Li; Chengfei Cao; Mohammad Ziaur Rahman; Xin Hu; Rujun Yu; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

3D-printed Al2O3 framework supported carbon-bridged tri-s-triazine of g-C3N4 for photocatalytic tetracycline oxidation - Chechia Hu; Lee-Lee Chang; Wei Chen; Wan-Yuan Hsu; Szu-Chia Chien; Chien-Hua Chen; Yu-Ting Lin; Tzu-Jung Hsu; Kuo-Lun Tung (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Endothelin-1-mediated Brainstem Glial Activation Produces Asthmatic Airway Vagal Hypertonia Via Enhanced ATP-P2X4 Receptor Signaling in Sprague–Dawley Rats - Yun Lin; Tian Liu; Hong Chen; Ming Zeng; Shunwei Hu; Xiaoning Yu; Yonghua Chen; Chunmei Xia; Jin Wang; Jijiang Wang (Journal of Neuroimmune Pharmacology, 2024)

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

Enhanced peroxymonosulfate (PMS) activation process mediated by vanadium modified CoO catalyst for rapid degradation of organic pollutants: Insights into the role of V - Yanting Jiang; Xin Weng; Yihui Hu; Yuancai Lv; Zhendong Yu; Yifan Liu; Xiaojuan Li; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

A hybrid system for Nickel ions removal from synthesized wastewater using adsorption assisted with electrocoagulation - Jean Claude Nizeyimana; Pamphile Ndagijimana; Junaid Khan; Liu Xiangru; Gratien Twagirayezu; Habasi Patrick Manzi; Olivier Irumva; Chang-Ping Yu; Anyi Hu; Shanshan Lin (Environmental Science and Pollution Research, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Dt1 inhibits SWEET-mediated sucrose transport to regulate photoperiod-dependent seed weight in soybean - Xiaoming Li; Zhonghui Chen; Haiyang Li; Lin Yue; Cuirong Tan; Hongjie Liu; Yilong Hu; Yuhua Yang; Xiani Yao; Lingping Kong; Xiang Huang; Bin Yu; et al. (Molecular Plant, 2024)

Sedimentary infill of Early-Middle Jurassic in the southeastern Tarim Basin and its constraints on the evolution of the Altyn Tagh Fault in the Northeast Tibet Plateau - Yu Xia; Xin Yang; Chenlin Hu; Huixi Lin; Hanao Li (Marine and Petroleum Geology, 2024)

Novel insights into aerobic 17β-estradiol degradation by enriched microbial communities from mangrove sediments - Shan Zhang; Xueying Ye; Xianbin Lin; Xiangwei Zeng; Shanshan Meng; Wenqi Luo; Fei Yu; Tao Peng; Tongwang Huang; Jin Li; Zhong Hu (Journal of Hazardous Materials, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Water in liquid crystal emulsion-based sensing platform for colorimetric detection of organophosphorus pesticide - Benyou Li; Wenli Wu; Jin-Ming Lin; Tao Wang; Qiongzheng Hu; Li Yu (Food Chemistry, 2024)

Interface engineering with ionic liquid for achieving efficient Quasi-2D perovskite light-emitting diodes - Kaiyu Yang; Baolin Xu; Qiuxiang Lin; Yongshen Yu; Hailong Hu; Fushan Li (Chemical Engineering Journal, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

An oxidized dextran-composite self-healing coated magnesium scaffold reduces apoptosis to induce bone regeneration - Zewen Shi; Fang Yang; Yiwei Hu; Qian Pang; Lin Shi; Tianyu Du; Yuhao Cao; Baiyang Song; Xueqiang Yu; Zhaoxun Cao; Zhewei Ye; Chen Liu; et al. (Carbohydrate Polymers, 2024)

Development of PEG-mediated genetic transformation and gene editing system of Bryum argenteum as an abiotic stress tolerance model plant - Fengjun Leng; Guiwei Zhou; Ruoyuan Shi; Chengyang Liu; Yirui Lin; Xinqiang Yu; Yanhua Zhang; Xiangxi He; Zhu Liu; Mingming Sun; Fang Bao; Yong Hu; et al. (Plant Cell Reports, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Distribution and sources of polycyclic aromatic hydrocarbons in surface sediments of the East China marginal seas: Significance of the terrestrial input and shelf mud deposition - Qi Shen; Huimin Yu; Yibo Cao; Zhigang Guo; Limin Hu; Lian Duan; Xueshi Sun; Tian Lin (Marine Pollution Bulletin, 2024)

Deoxynivalenol induced intestinal barrier injury, mitochondrial dysfunction and calcium overload by inositol 1,4,5-triphosphate receptors (IP3Rs)-mitochondrial calcium uniporter (MCU) calcium axis - Xin Li; Feiyang Gou; Jiang Zhu; Qian Lin; Minjie Yu; Xiaodian Tu; Qihua Hong; Caihong Hu (Science of The Total Environment, 2024)

Harnessing diurnal dynamics: Deciphering the interplay of light cycles on algal-bacterial membrane bioreactors - Sihan Cheng; Yuwei Zhang; Yu Zhao; Xin Hu; Hongjun Lin; Jiaheng Teng; Meijia Zhang (Science of The Total Environment, 2024)

Foraging behavior and sea ice-dependent factors affecting the bioaccumulation of mercury in Antarctic coastal waters - Lin Yang; Ben Yu; Hongwei Liu; Xiaomeng Ji; Cailing Xiao; Mengxi Cao; Jianjie Fu; Qinghua Zhang; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Science of The Total Environment, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Quantitative single-virus tracking for revealing the dynamics of SARS-CoV-2 fusion with plasma membrane - Hao-Yang Liu; Yusi Hu; Cong Yu; Zhi-Gang Wang; Shu-Lin Liu; Dai-Wen Pang (Science Bulletin, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Surface sediment erosion characteristics and influencing factors in the subaqueous delta of the abandoned Yellow River Estuary - Chaoran Lin; Rui Bao; Longhai Zhu; Rijun Hu; Jinlong Ji; Shilei Yu (Marine Geology, 2024)

Microbial metabolic flexibility guarantees function resilience in response to starvation disturbance - Yong-Chao Wang; Ya-Hui Lv; Xu-Rui Hu; Yu-Ting Lin; John C. Crittenden; Can Wang (Bioresource Technology, 2024)

Targeting Ferroptosis Promotes Functional Recovery by Mitigating White Matter Injury Following Acute Carbon Monoxide Poisoning - Shuhong Wang; Binyuan Xiong; Yin Tian; Quan Hu; Xuheng Jiang; Ji Zhang; Lin Chen; Ruilie Wang; Mo Li; Xin Zhou; Tianxi Zhang; Hongfei Ge; et al. (Molecular Neurobiology, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Application of nZnO supported with nanoclay for improving shrimp immunity - Zhen-Hao Liao; Chieh-Yuan Chuang; Yin-Yu Chen; Yu-Ting Chu; Yeh-Fang Hu; Po-Tsang Lee; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Interfacial Mo-S bond-reinforced hierarchical S-scheme heterostructure of Bi2MoO6@ZnIn2S4 for highly-selective and efficient CO2 photoreduction into CO - Jiale He; Jie Lin; Yu Zhang; Yingfei Hu; Qingling Huang; Guobing Zhou; Wei Li; Jianqiang Hu; Na Hu; Zhen Yang (Chemical Engineering Journal, 2024)

Reducing charge-recombination losses in photovoltaic cells by spontaneous reconstruction of n/p homojunction in a monolithic perovskite film using black phosphorus nanosheets - Lin Fan; Miao Yu; Wanting Hu; Lixue Wang; Zirui Mao; Fengyou Wang; Xiaoyan Liu; Xin Qu; Qiong Wu; Zhaoliang Yu; Lili Yang; Huilian Liu (Chemical Engineering Journal, 2024)

Compressible polydopamine modified pomelo peel powder/poly(ethyleneimine)/κ-carrageenan aerogel with pH-tunable charge for selective removal of anionic and cationic dyes - Jincheng Yu; Siyao Tian; Anrong Yao; Haoyi Hu; Jianwu Lan; Lin Yang; Xiaosheng Du; Shaojian Lin (Carbohydrate Polymers, 2024)

Potential roles of iron nanomaterials in enhancing growth and nitrogen fixation and modulating rhizomicrobiome in alfalfa (Medicago sativa L.) - Ming-Xu Zhang; Ling-Yu Zhao; Yuan-Yuan He; Jin-Peng Hu; Guo-Wen Hu; Ying Zhu; Aziz Khan; You-Cai Xiong; Jin-Lin Zhang (Bioresource Technology, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Anti-liquefaction mechanisms in buildings with shallow foundations with a focus on lowering the ground water table - Chih-Chieh Lu; Kuan-Yu Chen; Lin-Mao Hu; Wen-Yi Hung (Soil Dynamics and Earthquake Engineering, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Corncobs addition enhances the nitrogen removal in a constructed wetland for the disposal of secondary effluent from wastewater treatment plants - Mengni Tao; Yu Kong; Zhaoqian Jing; Lin Guan; Qiusheng Jia; Yiwei Shen; Meijia Hu (Journal of Water Process Engineering, 2023)

Algal strains, treatment systems and removal mechanisms for treating antibiotic wastewater by microalgae - Juan Peng; Kai-Lu Cao; Si-Bo Lv; Yu-Xuan Hu; Jia Lin; Qian-Zhi Zhou; Jiang-Hai Wang (Journal of Water Process Engineering, 2023)

Ultrasonic pretreatment-solvent extraction process for separating zinc from pickling waste liquid - Jiangpeng Zhang; Yu Lei; Shuxuan Hu; Xiong Li; Guo Lin; Shiwei Li (Journal of Environmental Chemical Engineering, 2023)

Quality changes and path analysis of color degradation of Dendrobium officinale flower juice during storage - Xuewen Dong; Jie Tang; Xiaoting Qin; Shenglan Tian; Huasi Lin; Qiang Yu; Xiaobo Hu; Mingyong Xie (Food Bioscience, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Sources of polychlorinated biphenyls (PCBs) in sediments of the East China marginal seas: Role of unintentionally-produced PCBs - Huimin Yu; Tian Lin; Limin Hu; Gerhard Lammel; Shizhen Zhao; Xueshi Sun; Xiao Wu; Zhigang Guo (Environmental Pollution, 2023)

Enhanced resuscitation of anammox granular sludge by adding folate: A perspective from the growth factor - Chao Pan; Leiyan Guo; Yang Yu; Wenji Li; Dongdong Xu; Wenda Chen; Lin Zhu; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Decoding the marine biogeochemical cycling of mercury by stable mercury isotopes - Lin Yang; Ben Yu; Deming Han; Kun Zhang; Hongwei Liu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Oyster shell for drinking water filtration compared with granular activated carbon: advantages and limitations - Huirong Lin; Quanyang Hou; Xiaohui Sun; Gongren Hu; Ruilian Yu (Environmental Science and Pollution Research, 2023)

Permafrost change and its engineering effects under climate change and airport construction scenarios in northeast China - Ming Guo; Yan Lu; Wenbing Yu; Lilin Xu; Da Hu; Lin Chen (Transportation Geotechnics, 2023)

Efficient decontamination of organic pollutants from wastewater by covalent organic framework-based materials - Zixuan Ma; Lin Fang; Lijie Liu; Baowei Hu; Suhua Wang; Shujun Yu; Xiangke Wang (Science of The Total Environment, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Efficient iron single-atom materials for environmental pollutants removal from aqueous solutions: A review - Hairui Hou; Lin Fang; Lijie Liu; Bing Zhao; Dedong Wu; Zixuan Ma; Baowei Hu; Xiangxue Wang; Shujun Yu (Journal of Cleaner Production, 2023)

Study on energy consumption, thermal comfort and economy of passive buildings based on multi-objective optimization algorithm for existing passive buildings - Yuanping Wang; Lang Hu; Lingchun Hou; Weiguang Cai; Lin Wang; Yu He (Journal of Cleaner Production, 2023)

Super-strong biomimetic bulk bamboo-based composites by a neural network interfacial design strategy - Juan Hu; Jieyu Wu; Yuxiang Huang; Yingqi He; Jian Lin; Yamei Zhang; Yahui Zhang; Yanglun Yu; Wenji Yu (Chemical Engineering Journal, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Smart enzyme-free amplification dual-mode self-powered platform designed on two-dimensional networked graphdiyne and DNA nanorods for ultra-sensitive detection of breast cancer biomarkers - Yunzhi Ma; Jinyue Shi; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Contrasting laboratory and field outcomes of bat–moth interactions - Aiqing Lin; Jiqian Li; Yinli Hu; Maojun Zhong; Minglun Yu; Nina Ma; Tingting Wei; Jinhong Luo; Jiang Feng (Molecular Ecology, 2023)
Predator–prey interactions are important but difficult to study in the field. Therefore, laboratory studies are often used to examine the outcomes of predator–prey interactions. Previous laboratory studies have shown that moth hearing and ultrasound production can help prey avoid being eaten by bats. We report here that laboratory behavioural outcomes may not accurately reflect the outcomes of field bat–moth interactions. We tested the success rates of two bat species capturing moths with distinct anti‐bat tactics using behavioural experiments. We compared the results with the dietary composition of field bats using next‐generation DNA sequencing. Rhinolophus episcopus and Rhinolophus osgoodi had a lower rate of capture success when hunting for moths that produce anti‐bat clicks than for silent eared moths and earless moths. Unexpectedly, the success rates of the bats capturing silent eared moths and earless moths did not differ significantly from each other. However, the field bats had a higher proportion of silent eared moths than that of earless moths and that of clicking moths in their diets. The difference between the proportions of silent eared moths and earless moths in the bat diets can be explained by the difference between their abundance in bat foraging habitats. These findings suggest that moth defensive tactics, bat countertactics and moth availability collectively shape the diets of insectivorous bats. This study illustrates the importance of using a combination of behavioural experiments and molecular genetic techniques to reveal the complex interactions between predators and prey in nature.

Digital Twin-enabled and Knowledge-driven decision support for tunnel electromechanical equipment maintenance - Gang Yu; Dinghao Lin; Yi Wang; Min Hu; Vijayan Sugumaran; Junjie Chen (Tunnelling and Underground Space Technology, 2023)

The SlARF4-SlHB8 regulatory module mediates leaf rolling in tomato - Xiaojuan Liu; Yuxiang Lin; Caiyu Wu; Yang Yang; Deding Su; Zhiqiang Xian; Yiyi Zhu; Canye Yu; Guojian Hu; Wei Deng; Zhengguo Li; Mondher Bouzayen; et al. (Plant Science, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Chloride removal from sewage using bismuth trioxide: Characterization and optimization by response surface methodology (RSM) - Liangjing Zhang; Yu Wang; Yunlong Liu; Shucong Lv; Rui Wang; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Kuixuan Lin; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Insight into the mechanism of water-insoluble dietary fiber from star anise (Illicium verum Hook. f.) on water-holding capacity of myofibrillar protein gels - Ying Xu; Jun Qi; Manman Yu; Ruishu Zhang; Hengxun Lin; Huimin Yan; Chao Li; Jingmin Jia; Yong Hu (Food Chemistry, 2023)

Hydrodynamic effects of the flow-induced vibrations on the mass transfer and permeate flux in a desalination membrane - Xiao Hu; Xinyu Li; Sanchuan Yu; Peifeng Lin; Zuchao Zhu (Desalination, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Self-assembled carrier-free nanomedicine suppresses tumor stemness to overcome the acquired drug-resistance of hepatocellular carcinoma - Huimin Lin; Qing Xu; Fang Zhang; Hualan Wu; Ben Hu; Guimei Chen; Xiaohua Ban; Xiaohui Duan; Meng Yu (Chemical Engineering Journal, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

PLK3 promotes the proneural–mesenchymal transition in glioblastoma via transcriptional regulation of C5AR1 - Shuo Yu; Lin Lv; Yang Li; Qian Ning; Tingting Liu; Tinghua Hu (Molecular Biology Reports, 2023)

Association of air pollutants and meteorological factors with tuberculosis: a national multicenter ecological study in China - Qian Wang; Yan-lin Li; Ya-ling Yin; Bin Hu; Chong-chong Yu; Zhen-de Wang; Yu-hong Li; Chun-jie Xu; Yong-bin Wang (International Journal of Biometeorology, 2023)

A highly sensitive self-powered sensing method designed on DNA circuit strategy and MoS2 hollow nanorods for detection of thalassemia - Jinyue Shi; Danyao Tang; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

CAS FGOALS-f3-L Model Datasets for CMIP6 DCPP Experiment - Shuai Hu; Bo Wu; Yiming Wang; Tianjun Zhou; Yongqiang Yu; Bian He; Pengfei Lin; Qing Bao; Hailong Liu; Kangjun Chen; Shuwen Zhao (Advances in Atmospheric Sciences, 2023)
The outputs of the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System (FGOALS-f3-L) model for the decadal climate prediction project (DCPP) of the Coupled Model Intercomparison Project Phase 6 (CMIP6) are described in this paper. The FGOALS-f3-L was initialized through the upgraded, weakly coupled data assimilation scheme, referred to as EnOI-IAU, which assimilates observational anomalies of sea surface temperature (SST) and upper-level (0–1000-m) ocean temperature and salinity profiles into the coupled model. Then, nine ensemble members of 10-year hindcast/forecast experiments were conducted for each initial year over the period of 1960–2021, based on initial conditions produced by three initialization experiments. The hindcast and forecast experiments follow the experiment designs of the Component-A and Component-B of the DCPP, respectively. The decadal prediction output datasets contain a total of 44 monthly mean atmospheric and oceanic variables. The preliminary evaluation indicates that the hindcast experiments show significant predictive skill for the interannual variations of SST in the north Pacific and multi-year variations of SST in the subtropical Pacific and the southern Indian Ocean.

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

Heavy metal contamination collapses trophic interactions in the soil microbial food web via bottom-up regulation - Xuehua Wang; Zhongmin Dai; Jiahui Lin; Haochun Zhao; Haodan Yu; Bin Ma; Lingfei Hu; Jiachun Shi; Xiaoyun Chen; Manqiang Liu; Xin Ke; Yijun Yu; et al. (Soil Biology and Biochemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Polyphenolic glycosides with unusual four-membered ring possessing anti-Parkinson's disease potential from black wolfberry - Yi-Kao Hu; Xiao-Lin Bai; Guang-Yu Shi; Yong-Mei Zhang; Xun Liao (Phytochemistry, 2023)

A digital twin-based framework for simulation and monitoring analysis of floating wind turbine structures - Yi Liu; Jian-Min Zhang; Yan-Tao Min; Yantao Yu; Chao Lin; Zhen-Zhong Hu (Ocean Engineering, 2023)

Characterizing annual dynamics of urban form at the horizontal and vertical dimensions using long-term Landsat time series data - Yixuan Wang; Xuecao Li; Peiyi Yin; Guojiang Yu; Wenting Cao; Jinxiu Liu; Lin Pei; Tengyun Hu; Yuyu Zhou; Xiaoping Liu; Jianxi Huang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Emulsions containing composite (clove, oregano, and cinnamon) essential oils: Phase inversion preparation, physicochemical properties and antibacterial mechanism - Jiajie Hu; Hangxin Zhu; Yuwei Feng; Mijia Yu; Yueqiang Xu; Yadong Zhao; Bin Zheng; Jiheng Lin; Wenhua Miao; Rusen Zhou; Patrick J. Cullen (Food Chemistry, 2023)

Fermentation of grapefruit peel by an efficient cellulose-degrading strain, (Penicillium YZ-1): Modification, structure and functional properties of soluble dietary fiber - Wenjie Ma; Yuting Liang; Huasi Lin; Yi Chen; Jianhua Xie; Fengling Ai; Ziwen Yan; Xiaobo Hu; Qiang Yu (Food Chemistry, 2023)

Periodate activation by atomically dispersed Mn on carbon nanotubes for the production of iodate radicals and rapid degradation of sulfadiazine - Jiahui Hu; Yubin Zou; Yin Li; Zehui Yu; Yutian Bao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Combination of surfactants and enzyme cocktails for enhancing woody biomass saccharification and bioethanol production from lab-scale to pilot-scale - Wei Qi; Qifa Feng; Wen Wang; Yu Zhang; Yunzi Hu; Usama Shakeel; Lin Xiao; Lan Wang; Hongzhang Chen; Cuiyi Liang (Bioresource Technology, 2023)

Acorus calamus recycled as an additional carbon source in a microbial fuel cell-constructed wetland for enhanced nitrogen removal - Mengni Tao; Yu Kong; Zhaoqian Jing; Lin Guan; Qiusheng Jia; Yiwei Shen; Meijia Hu; Yu-You Li (Bioresource Technology, 2023)

Reprogramming the fatty acid metabolism of Yarrowia lipolytica to produce the customized omega-6 polyunsaturated fatty acids - Jinpeng Wang; Xiao Yu; Kaifeng Wang; Lu Lin; Hu-Hu Liu; Rodrigo Ledesma-Amaro; Xiao-Jun Ji (Bioresource Technology, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

Phenolic compound profile and gastrointestinal action of Solanaceae fruits: Species-specific differences - Changan Zhu; Min Zhang; Shuwen Wang; Xinhao Gao; Teng Lin; Jingquan Yu; Jinhu Tian; Zhangjian Hu (Food Research International, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Different grazers and grazing practices alter the growth, soil properties, and rhizosphere soil bacterial communities of Medicago ruthenica in the Qinghai-Tibetan Plateau grassland - Ming-Xu Zhang; Ling-Yu Zhao; Jin-Peng Hu; Aziz Khan; Xiao-Xia Yang; Quan-Min Dong; Christopher Rensing; Xiang-Ling Fang; Jin-Lin Zhang (Agriculture, Ecosystems & Environment, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Cobalt induces neurodegeneration through FTO-triggered autophagy impairment by targeting TSC1 in an m6A-YTHDF2-dependent manner - Jianping Tang; Fuli Zheng; Xu Liu; Yanjun Li; Zhenkun Guo; Xinpei Lin; Jinfu Zhou; Yu Zhang; Guangxia Yu; Hong Hu; Wenya Shao; Siying Wu; et al. (Journal of Hazardous Materials, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Swc4 protects nucleosome-free rDNA, tDNA and telomere loci to inhibit genome instability - Yue Pan; Can Hu; Lin-Jun Hou; Yu-Long Chen; Jiantao Shi; Jia-Cheng Liu; Jin-Qiu Zhou (DNA Repair, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

Engineering highly efficient NIR-II FRET platform for Background-Free homogeneous detection of SARS-CoV-2 neutralizing antibodies in whole blood - Lei Zhao; Qingwei Song; Weikang Mai; Min Deng; Yu Lei; Lu Chen; Weiya Kong; Lei Zhang; Lin Zhang; Yantao Li; Huiru Ye; Yiru Qin; et al. (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Source apportionment and transfer characteristics of Pb in a soil-rice-human system, Jiulong River Basin, southeast China - Chengqi Lin; Yanyun Wang; Gongren Hu; Ruilian Yu; Huabin Huang (Environmental Pollution, 2023)

Ultralow Ru loading RuO2-TiO2 with strong oxide-support interaction for efficient chlorine evolution and ammonia-nitrogen-elimination - Mengchen Hu; Tianqi Yu; Kexin Tan; Anchao Zhou; Lin Luo; Shibin Yin (Chemical Engineering Journal, 2023)

Superior sorption capacity and one-step reduction of Au(III) by a novel chitosan-based electrospun fiber mat: A cheap and simple technique - Chuanhao Yan; Xuefeng Yu; Wenyi Jia; Jinglei He; Jing Hu; Meng Zhang; Jianlong Wang; Lin Tang; Junfeng Liu; Xilong Wang (Chemical Engineering Journal, 2023)

Retraction Note: MicroRNA-20b suppresses the expression of ZFP-148 in viral myocarditis - Hong-Fei Xu; Xiang-Ting Gao; Jun-Yi Lin; Xue-Hua Xu; Jun Hu; Yu-Jie Ding; Shao-Hua Zhu (Molecular and Cellular Biochemistry, 2023)

Kungurian sedimentary environments in the slope facies of the Xuyong area, South China, and a comparative analysis of low-latitude palaeogeography - Liangjun Wu; Haixian Jiang; Ming Pan; Pujun Wang; Jingsong Hu; Jiwen Wu; Yu Lin; Wenqiang Shi (Carbonates and Evaporites, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

To close or open the tank input water valve: Secondary water-supply systems with double tanks will induce a higher microbial risk - Dong Hu; Wenfang Lin; Jie Zeng; Heng Zhang; Yating Wei; Xin Yu (Science of The Total Environment, 2023)

Coating zero valent iron onto hollow carbon spheres as efficient electrocatalyst for N2 fixation and neutral Zn-N2 battery - Huici Qiao; Yu Han; Lin Yao; Xin Xu; Jun Ma; Bin Wen; Jie Hu; Hao Huang (Chemical Engineering Journal, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Dietary chitosan alleviates intestinal and liver injury of hybrid sturgeon (Acipenser baerii♀ × A. schrenckii♂) induced by Aeromonas hydrophila infection - Ruiran Li; Xiaoni Wang; Denghang Yu; Qianrong Liang; Fuguo Liu; Lin Zhang; Bing Hu; Jin Wei; Lihe Liu; Jun Liu; Hongsen Xu (Animal Feed Science and Technology, 2023)

Hydrogen injection reduces ammonia nitrogen and changes microbial community composition in aquaculture water - Shengdi Ning; Junru Hu; Jie Yu; Long Huang; Minjian Lai; Xiangni Li; Yongchun Lin; Wanqing Zhong; Lei Wang (Frontiers in Marine Science, 2023)
The study aimed to investigate the effect of hydrogen on nitrogen and phosphorus removal and microbial community composition in aquaculture water. Two groups were designed separated: Group H was charged with hydrogen and Group D was set as control. Water samples were collected at 0, 1, 2, 3, 4, 5, 6, and 7 days after hydrogen injection to detect not only the content of total nitrogen, ammonia nitrogen and phosphorus, but also microbial community composition in aquaculture water. Our findings have demonstrated that 7-days’ hydrogen treatment could effectively reduce ammonia nitrogen in aquaculture water. And in Day 7, the concentration of ammonia nitrogen in Group D was 1.66 times as that in Group H. Meanwhile, microbial structures in the water bodies of these two groups were significantly different. The abundance of bacteria such as Proteobacteria, Firmicutes, Bacteroidetes, and Desulphuri a increased clearly in Group H, which means nitrification and denitrification occurred in the effect of hydrogen injection. These findings suggested that hydrogen could significantly improve aquaculture water health and reduce the production of ammonia nitrogen, which means hydrogen could be used as a functional external method to protect the aquaculture environment.

Studies on the interaction of five triazole fungicides with human renal transporters in cells - Jing Nie; Jiabei Zhou; Yi Shen; Ruimiao Lin; Haihong Hu; Kui Zeng; Huichang Bi; Min Huang; Lushan Yu; Su Zeng; Jing Miao (Toxicology in Vitro, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

An overview on constructed wetland-microbial fuel cell: Greenhouse gases emissions and extracellular electron transfer - Liangjing Zhang; Yunlong Liu; Shucong Lv; Rui Wang; Yu Wang; Kuixuan Lin; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeus vannamei - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Chi-Yun Hu; Yu-Hsuan Kai; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2023)

Polystyrene microplastics arrest skeletal growth in puberty through accelerating osteoblast senescence - Chun Pan; Yin Wu; Sihan Hu; Ke Li; Xiangyu Liu; Yu Shi; Wenzheng Lin; Xinglong Wang; Yujie Shi; Zhuobin Xu; Huihui Wang; Hao Chen (Environmental Pollution, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Ultrasensitive amperometric determination of hand, foot and mouth disease based on gold nanoflower modified microelectrode - Yu Zhong; Xiang-Guang Hu; Ai-Lin Liu; Yun Lei (Analytica Chimica Acta, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Roles of radical species in vacuum-UV/UV/peroxydisulfate advanced oxidation processes and contributions of the species to contaminant degradation at different water depths - Yu-Jia Nong; Yi-Lin Zhang; Uwe Hübner; Wen-Long Wang; Qian-Yuan Wu; Nan Huang; Jörg E. Drewes; Hong-Ying Hu (Journal of Hazardous Materials, 2023)

Microbiological quality of roof tank water in an urban village in southeastern China - Dong Hu; Jie Zeng; Jing Chen; Wenfang Lin; Xinyan Xiao; Mingbao Feng; Xin Yu (Journal of Environmental Sciences, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Transformation of soil organic matter subjected to environmental disturbance and preservation of organic matter bound to soil minerals: a review - Qingchao Li; Lingli Wang; Yu Fu; Dagang Lin; Meiru Hou; Xiaodie Li; Dongdong Hu; Zhaohui Wang (Journal of Soils and Sediments, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Mei-Jie Yang; Ying Shi; Zhi-Shu Lin; Pu Shi; Zhi Hu; Cong Zhou; Peng-Peng Hu; Zheng-Lin Yu; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa , but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa . This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa , which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.

Sequential combination of pre-chlorination and powdered activated carbon adsorption on iodine removal and I-THMs control in drinking water - Renjie Pan; Yi-Li Lin; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Chemosphere, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Handwipes as indicators to assess organophosphate flame retardants exposure and thyroid hormone effects in e-waste dismantlers - Jian Tang; Shengtao Ma; Xin Hu; Meiqing Lin; Guiying Li; Yingxin Yu; Taicheng An (Journal of Hazardous Materials, 2023)

Single-atom Co-N3 sites supported on waste paper-derived active carbon for synergistic adsorption and catalytic degradation of antibiotics - Mengying Qian; Meichi Lu; Minjia Yan; Chaofa Chen; Yuwen Hu; Yu Li; Jianrong Chen; Xi-Lin Wu (Journal of Environmental Chemical Engineering, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Occurrence, distribution, and characteristics of microplastics in agricultural soil around a solid waste treatment center in southeast China - Xi Liu; Huirong Lin; Sheng Xu; Yu Yan; Ruilian Yu; Gongren Hu (Journal of Soils and Sediments, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Associations between long-term exposure to ambient fine particulate pollution with the decline of kidney function and hyperuricemia: a longitudinal cohort study - Li-Kun Hu; Yu-Hong Liu; Kun Yang; Ning Chen; Lin-Lin Ma; Yu-Xiang Yan (Environmental Science and Pollution Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Assessment of factors affecting the diurnal variations of atmospheric PAHs based on a numerical simulation - Zhongxiu Zhen; Yan Yin; Haowen Zhang; Jingyi Li; Jianlin Hu; Lin Li; Xiang Kuang; Kui Chen; Honglei Wang; Qingyuan Yu; Xin Zhang (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Microbiome reengineering by four environmental factors for the rapid biodegradation of trichloroethylene - Yu-Hsuan Cheng; Shu-Chi Chang; Yan-Lin Lai; Chung-Chi Hu (Journal of Environmental Management, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

The association of long-term ambient fine particulate matter exposure with blood pressure among Chinese adults - Zhennan Lin; Shufeng Chen; Fangchao Liu; Jianxin Li; Jie Cao; Keyong Huang; Fengchao Liang; Jichun Chen; Hongfan Li; Jianfeng Huang; Dongsheng Hu; Chong Shen; et al. (Environmental Pollution, 2023)

Copper sulfide engineered covalent organic frameworks for pH-responsive chemo/photothermal/chemodynamic synergistic therapy against cancer - Shuangling Wang; Yu Pang; Shuyang Hu; Jie Lv; Yulong Lin; Meng Li (Chemical Engineering Journal, 2023)

Functionalized graphene oxide/sodium alginate beads with ion responsiveness for uranium trapping - Yu Nan; Jianli Wang; Xue Chang; Kejin Shao; Yuchen Lin; Lijuan Qian; Zhan Li; Peizhuo Hu (Carbohydrate Polymers, 2023)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Uncertainty in Atlantic Multidecadal Oscillation derived from different observed datasets and their possible causes - Bowen Zhao; Pengfei Lin; Aixue Hu; Hailong Liu; Mengrong Ding; Zipeng Yu; Yongqiang Yu (Frontiers in Marine Science, 2022)
As a leading mode of sea surface temperature (SST) variability over the North Atlantic in both observations and model simulations, the Atlantic Multidecadal Oscillation (AMO) can have a substantial influence on regional and global climate. By using Low-Frequency Component Analysis, we explore the uncertainties of the resulting AMO indices and the corresponding spatial patterns derived from three observational SST datasets. We found that the known coherent spatial pattern of the AMO at the basin scale over the North Atlantic appears in two out of the three datasets. Further analysis indicates that both the warming trend and the different techniques used to construct these observed gridded SSTs contribute to the AMO’s spatial coherence over the North Atlantic, especially during periods of sparse data sampling. The SST in the Extended Reconstructed SST dataset version 5 (ERSSTv5), changes from being systematically below the other datasets during the dense sampling periods on either side of the Second World War (WWII), to systematically above the other datasets during WWII, thereby introducing an artificial 10–20-year variability that affects the AMO’s spatial coherence. This coherence in the AMO’s spatial pattern is also affected by bias adjustment in ERSSTv5 at relative cool (i.e., non-summer) seasons, and by the heterogeneous North Atlantic warming pattern. The different AMO patterns can induce the different effects of wind, surface heat fluxes, and then drive ocean circulation and its heat transport convergence, especially for some seasons. For AMO indices, both the different detrending methods and different observational data result in uncertainty for the period 1935–1950. Such SST uncertainty is important to detect the relative role of the atmosphere and ocean in shaping the AMO.

Vitamin D regulates transepithelial acid secretion in zebrafish (Danio rerio) larvae - Chia-Hao Lin; Sian-Tai Liu; Yu-Chun Wang; Yi-Ling Tsou; Huei-Jyun Hu (Frontiers in Marine Science, 2022)
Maintenance of an acid-base balance is essential for normal physiological processes in vertebrates. Freshwater fishes live in an aquatic environment with variable pH, and their buffering capacity for acid-base balance in body fluids is weak. Thus, after acid exposure, fishes secrete excess acid to prevent internal acidosis. Acid-secreting ionocytes present in the adult gills and embryonic skin are primarily responsible for acid secretion, and H + -ATPase and Na + /H + exchanger 3 (NHE3) are the two main transporters responsible for apical acid secretion. Vitamin D is a well-known hormone involved in the maintenance of Ca 2+ homeostasis and is suggested to be involved in acid-base regulation by modulating the activity and/or mRNA expression of NHE3 in mammalian models. It remains unclear whether vitamin D is involved in acid secretion in fishes. The aim of the present study was to use zebrafish as a model to determine whether vitamin D and its receptors influence acid secretion. Our results indicated that the levels of 1α, 25-dihydroxyvitamin D 3 (1α,25(OH) 2 D 3 ), the bioactive vitamin D, were significantly increased in 3 days post-fertilization zebrafish larvae after exposure to acidic freshwater (AFW, pH 4.0). Exogenous 1α,25(OH) 2 D 3 (20 μg/L) incubation substantially enhanced the mRNA expression of acid-secreting transporters and acid secretion at the skin of the entire body and each H + -ATPase-rich cell (HRC), a type of acid-secreting ionocyte. Furthermore, the expression of vitamin D receptors (VDRs) was identified in HRCs of zebrafish. When both VDRa and VDRb were knocked down, acid secretion and the mRNA expression of acid-secreting transporters were significantly decreased. Moreover, double knockdown of VDRa/b prevented the increase in acid secretion induced by AFW and 1α,25(OH) 2 D 3 treatment. This study is the first to indicate that vitamin D is involved in acid secretion in fish.

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Transgenic expression of rice OsPHR2 increases phosphorus uptake and yield in wheat - Yan Li; Yuhui Fang; Chaojun Peng; Xia Hua; Yu Zhang; Xueli Qi; Zhengling Li; Yumin Wang; Lin Hu; Weigang Xu (Protoplasma, 2022)

Cross-generation trophic ecology of Dosidicus gigas in the eastern-central Pacific Ocean revealed from isotopic signatures in eye lenses - Guan Yu Hu; Zi Xin Wang; Bi Lin Liu; Meng Yao Huan; Xin Jun Chen (Fisheries Science, 2022)

Transformation of HBCDs by Rhodococcus sp. stu-38 - Fei Yu; Wenqi Luo; Yuyang Li; Shanshan Meng; Xianbin Lin; Lele Li; Xueying Ye; Hui Wang; Tao Peng; Tongwang Huang; Zhong Hu (Current Microbiology, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Epidemiological characteristics of gonorrhea and its influential meteorological factors: a 14-year retrospective assessment in China - Jin Bu; Liang-Jia Zhou; Xiang Xiao; Qian Yue; Gang Hu; Pei Jiang; Jing Chen; Yu Lin (Environmental Science and Pollution Research, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Selenium Alleviates Inflammation in Staphylococcus aureus-Induced Mastitis via MerTK-Dependent Activation of the PI3K/Akt/mTOR Pathway in Mice - Si-jie Chen; Chen-yuan Zhang; Di Yu; Chang-jie Lin; Hao-jun Xu; Chang-min Hu (Biological Trace Element Research, 2022)

Frequency design of LEO-based navigation augmentation signals for dual-band ionospheric-free ambiguity resolution - Fujian Ma; Xiaohong Zhang; Jiahuan Hu; Pan Li; Lin Pan; Siqi Yu; Zhiyu Zhang (GPS Solutions, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Termite mound formation reduces the abundance and diversity of soil resistomes - Zhen‐Zhen Yan; Qing‐Lin Chen; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong‐Guan Zhu; Ji‐Zheng He; Hang‐Wei Hu (Environmental Microbiology, 2021)
Summary Termites are pivotal ecosystem engineers in tropical and subtropical habitats, where they construct massive nests (‘mounds’) that substantially modify soil properties and promote nutrient cycling. Yet, little is known about the roles of termite nesting activity in regulating the spread of antimicrobial resistance (AMR), one of the major Global Health challenges. Here, we conducted a large‐scale (> 1500 km) investigation in northern Australia and found distinct resistome profiles in termite mounds and bulk soils. By profiling a wide spectrum of ARGs, we found that the abundance and diversity of antibiotic resistance genes (ARGs) were significantly lower in termite mounds than in bulk soils ( P P

Precipitation increases the abundance of fungal plant pathogens in Eucalyptus phyllosphere - Qing‐Lin Chen; Hang‐Wei Hu; Zhen‐Zhen Yan; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong‐Guan Zhu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Understanding the current and future distributions of plant pathogens is critical to predict the plant performance and related economic benefits in the changing environment. Yet, little is known about the roles of environmental drivers in shaping the profiles of fungal plant pathogens in phyllosphere, an important habitat of microbiomes on Earth. Here, using a large‐scale investigation of Eucalyptus phyllospheric microbiomes in Australia and the multiple linear regression model, we show that precipitation is the most important predictor of fungal taxonomic diversity and abundance. The abundance of fungal plant pathogens in phyllosphere exhibited a positive linear relationship with precipitation. With this empirical dataset, we constructed current and future atlases of phyllosphere plant pathogens to estimate their spatial distributions under different climate change scenarios. Our atlases indicate that the abundance of fungal plant pathogens would increase especially in the coastal regions with up to 100‐fold increase compared with the current abundance. These findings advance our understanding of the distributions of fungal plant pathogens in phyllospheric microbiomes under the climate change, which can improve our ability to predict and mitigate their impacts on plant productivity and economic losses.

Development and validation of gene-specific KASP markers for YrAS2388R conferring stripe rust resistance in wheat - Yanling Hu; Xuhui Huang; Fang Wang; Yu He; Lihua Feng; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; Jiajie Wu; Lianquan Zhang; Bihua Wu; et al. (Euphytica, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

Effects of periodically varying codes on separation of multisource blended data - Meng-Yao Jiao; Tian-Yue Hu; Yang Liu; Zhen-Zhen Yu; Shang-Lin Liang; Li-Chao Liu; Ji-Wei (Applied Geophysics, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Game strategies in government-led eco-compensation in the Xin’an River Basin from the perspective of the politics of scale - Yisheng Ren; Lin Lu; Hu Yu; Daocai Zhu (Journal of Geographical Sciences, 2021)

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

A dye combination for the staining of pollen coat and pollen wall - Xin-Lei Jia; Jing-Shi Xue; Fang Zhang; Chi Yao; Shi-Yi Shen; Chang-Xu Sui; Yu-Jia Peng; Qin-Lin Xu; Yi-Feng Feng; Wen-Jing Hu; Ping Xu; Zhong-Nan Yang (Plant Reproduction, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Termite mounds reduce soil microbial diversity by filtering rare microbial taxa - Qing‐Lin Chen; Hang‐Wei Hu; Zhen‐Zhen Yan; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong Zheng; Yong‐Guan Zhu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Termites are ubiquitous insects in tropical and subtropical habitats, and some of them construct massive nests (‘mounds’), which substantially promote substrate heterogeneity by altering soil properties. Yet, the role of termite nesting process in regulating the distribution and diversity of soil microbial communities remains poorly understood, which introduces uncertainty in predictions of ecosystem functions of termite mounds in a changing environment. Here, by using amplicon sequencing, we conducted a survey of 134 termite mounds across >1500 km in northern Australia and found that termite mounds significantly differed from bulk soils in the microbial diversity and community compositions. Compared with bulk soils, termite nesting process decreased the microbial diversity and the relative abundance of rare taxa. Rare taxa had a narrower habitat niche breadth than dominant taxa and might be easier to be filtered by the potential intensive microbial competition during the nesting processes. We further demonstrated that the shift in pH induced by termite nesting process was a major driver shaping the microbial community profiles in termite mounds. Together, our work provides novel evidence that termite nesting is an important process in regulating soil microbial diversity, which advances our understanding of the functioning of termite mounds.

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

Calcium signalling mediated the regulation of growth and polysaccharide accumulation by light quality in Dendrobium officinale protocorms - Ting Lei; Suping Gao; Xiao Lin; Kaihui Zhang; Yingqi Liu; Wenji Li; Di Hu; Xiaofang Yu; Mingyan Jiang; Qibing Chen; Ying Sun (Horticulture, Environment, and Biotechnology, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

A study on the application of the distributed optical fiber sensing monitoring technology in the process of dismantling temporary tunnel shoring - Zi-Xiang Li; Gong-Yu Hou; Tao Hu; Tian-Ci Zhou; Hai-Lin Xiao (Arabian Journal of Geosciences, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

The interaction between dietary marine components and intestinal flora - Lin Li; Chang-Hu Xue; Tian-Tian Zhang; Yu-Ming Wang (Marine Life Science & Technology, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Grass carp (Ctenopharyngodon idella) Bcl-xl: transcriptional regulation and anti-apoptosis analysis - Guoqin Qi; Ningli Yu; Kang Xu; Xiaofen Xie; Yuexin Mao; Xin Chen; Xiaoqin Ran; Xingxing Chen; Gang Lin; Chengyu Hu (Fish Physiology and Biochemistry, 2020)

A survey of microbial contamination in aviation fuel from aircraft fuel tanks - Dong Hu; Jie Zeng; Shangshu Wu; Xi Li; Chengsong Ye; Wenfang Lin; Xin Yu (Folia Microbiologica, 2020)

Swelling characteristics of andesite foundation induced by water immersion and their influence on ballastless track subgrade - Jun-yi Duan; Guo-lin Yang; Min Hu; Xiao-qin Lei; Yu-liang Lin (Journal of Mountain Science, 2020)

MicroRNA-mediated responses to colchicine treatment in barley - Fang-Yao Sun; Lin Liu; Yi Yu; Xin-Ming Ruan; Cheng-Yu Wang; Qun-Wen Hu; De-Xiang Wu; Genlou Sun (Planta, 2020)

Dolphin-watching tourism and indo-Pacific humpback dolphins (Sousa chinensis) in Sanniang Bay, China: impacts and solutions - Haiping Wu; Chongwei Peng; Hu Huang; Thomas A. Jefferson; Shiang-Lin Huang; Mo Chen; Qianhui Zeng; Xueying Yu; Xianyan Wang; Youhou Xu (European Journal of Wildlife Research, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Chronic ketamine abuse is associated with orexin-A reduction and ACTH elevation - Ming-Chyi Huang; Chun-Hsin Chen; Lian-Yu Chen; Hu-Ming Chang; Chih-Ken Chen; Shih-Ku Lin; Ke Xu (Psychopharmacology, 2020)

Concomitant biocontrol of pepper Phytophthora blight by soil indigenous arbuscular mycorrhizal fungi via upfront film-mulching with reductive fertilizer and tobacco waste - Shaowei Hou; Yu Zhang; Minghui Li; Homgmin Liu; Fuyong Wu; Junli Hu; Xiangui Lin (Journal of Soils and Sediments, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Investigating the Transport Mechanism of PM2.5 Pollution during January 2014 in Wuhan, Central China - Miaomiao Lu; Xiao Tang; Zifa Wang; Lin Wu; Xueshun Chen; Shengwen Liang; Hui Zhou; Huangjian Wu; Ke Hu; Longjiao Shen; Jia Yu; Jiang Zhu (Advances in Atmospheric Sciences, 2019)
Severe haze pollution that occurred in January 2014 in Wuhan was investigated. The factors leading to Wuhan’s PM 2.5 pollution and the characteristics and formation mechanism were found to be significantly different from other megacities, like Beijing. Both the growth rates and decline rates of PM 2.5 concentrations in Wuhan were lower than those in Beijing, but the monthly PM 2.5 value was approximately twice that in Beijing. Furthermore, the sharp increases of PM 2.5 concentrations were often accompanied by strong winds. A high-precision modeling system with an online source-tagged method was established to explore the formation mechanism of five haze episodes. The long-range transport of the polluted air masses from the North China Plain (NCP) was the main factor leading to the sharp increases of PM 2.5 concentrations in Wuhan, which contributed 53.4% of the monthly PM 2.5 concentrations and 38.5% of polluted days. Furthermore, the change in meteorological conditions such as weakened winds and stable weather conditions led to the accumulation of air pollutants in Wuhan after the long-range transport. The contribution from Wuhan and surrounding cities to the PM 2.5 concentrations was determined to be 67.4% during this period. Under the complex regional transport of pollutants from surrounding cities, the NCP, East China, and South China, the five episodes resulted in 30 haze days in Wuhan. The findings reveal important roles played by transregional and intercity transport in haze formation in Wuhan.

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

Profiling the microbial contamination in aviation fuel from an airport - Dong Hu; Wenfang Lin; Jie Zeng; Peng Wu; Menglu Zhang; Lizheng Guo; Chengsong Ye; Kun Wan; Xin Yu (Biofouling, 2019)

Correction to: Occurrence of 25 pharmaceuticals in Taihu Lake and their removal from two urban drinking water treatment plants and a constructed wetland - Xia-Lin Hu; Yi-Fan Bao; Jun-Jian Hu; You-Yu Liu; Da-Qiang Yin (Environmental Science and Pollution Research, 2019)

The Eurasian Jet Streams as Conduits for East Asian Monsoon Variability - Jasti S. Chowdary; Kaiming Hu; G. Srinivas; Yu Kosaka; Lin Wang; K. Koteswara Rao (Current Climate Change Reports, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Evaluation of particulate matter deposition in the human respiratory tract during winter in Nanjing using size and chemically resolved ambient measurements - Xiaoyuan Liu; Dongyang Nie; Kai Zhang; Ziyao Wang; Xiaoqian Li; Zhihao Shi; Yiyi Wang; Lin Huang; Mindong Chen; Xinlei Ge; Qi Ying; Xingna Yu; et al. (Air Quality, Atmosphere & Health, 2019)

Magma–magma interaction in the mantle recorded by megacrysts from Cenozoic basalts in eastern China - Xun Yu; Gang Zeng; Li-Hui Chen; Sen-Lin Hu; Zhi-Qiang Yu (International Geology Review, 2019)

Distribution and provenance implication of rare earth elements and Sr-Nd isotopes in surface sediments of Jiulong River, Southeast China - Ruilian Yu; Chengqi Lin; Yu Yan; Gongren Hu; Huabin Huang; Xiaoming Wang (Journal of Soils and Sediments, 2019)

Quaternary phosphonium cationic ionic liquid/porous metal–organic framework as an efficient catalytic system for cycloaddition of carbon dioxide into cyclic carbonates - Yu Lin Hu; Rui Li Zhang; Dong Fang (Environmental Chemistry Letters, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Mechanistic studies of the apoptosis induced by the macrocyclic natural product tetrandrine in MGC 803 cells - Sai-Qi Wang; Hong-Lin Hou; Liang-Yu Bie; Cai-Yun Nie; Luo-Nan Wang; Shaobing Gao; Ting-Ting Hu; Xiao-Bing Chen (Medicinal Chemistry Research, 2019)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Reduced connection between the East Asian Summer Monsoon and Southern Hemisphere Circulation on interannual timescales under intense global warming - Tianlei Yu; Pinwen Guo; Jun Cheng; Aixue Hu; Pengfei Lin; Yongqiang Yu (Climate Dynamics, 2018)

A Novel MYCN Variant Associated with Intellectual Disability Regulates Neuronal Development - Xiuya Yu; Liyuan Hu; Xu Liu; Guodong Zhan; Mei Mei; Huijun Wang; Xiaohua Zhang; Zilong Qiu; Wenhao Zhou; Lin Yang (Neuroscience Bulletin, 2018)

Deformation process and mechanism analyses for a planar sliding in the Mayanpo massive bedding rock slope at the Xiangjiaba Hydropower Station - Shi-lin Zhang; Zhao-hui Zhu; Shun-chao Qi; Yu-xiang Hu; Qing Du; Jia-wen Zhou (Landslides, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

A unique genetic lineage at the southern coast of China in the agar-producing Gracilaria vermiculophylla (Gracilariales, Florideophyceae) - Zi-Min Hu; Ruo-Yu Liu; Jie Zhang; De-Lin Duan; Gao-Ge Wang; Wen-Hong Li (Algae, 2018)

Genetic analysis and QTL mapping of fruit-related traits in wax gourd (Benincasa hispida) - Wenrui Liu; Biao Jiang; Qingwu Peng; Xiaoming He; Yu’e Lin; Min Wang; Zhaojun Liang; Dasen Xie; Kailin Hu (Euphytica, 2018)

Physical Stability of Amorphous Solid Dispersions: a Physicochemical Perspective with Thermodynamic, Kinetic and Environmental Aspects - Xia Lin; Yang Hu; Lei Liu; Lili Su; Na Li; Jing Yu; Bo Tang; Ziyi Yang (Pharmaceutical Research, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

Converting natural evergreen broadleaf forests to intensively managed moso bamboo plantations affects the pool size and stability of soil organic carbon and enzyme activities - Ziwen Lin; Yongfu Li; Caixian Tang; Yu Luo; Weijun Fu; Xiaoqing Cai; Yongchun Li; Tian Yue; Peikun Jiang; Shuaidong Hu; Scott X. Chang (Biology and Fertility of Soils, 2018)

A late Pleistocene marine glacial refugium in the south‐west of Hainan Island, China: Phylogeographical insights from the brown alga Sargassum polycystum - Zi‐Min Hu; Attachai Kantachumpoo; Ruo‐Yu Liu; Zhong‐Min Sun; Jian‐Ting Yao; Teruhisa Komatsu; Shinya Uwai; De‐Lin Duan (Journal of Biogeography, 2018)
Aim Hainan Island, southern China, is characterized by rich diversity and endemism of marine organisms, yet the underpinning mechanisms and processes contributing to speciation and diversification are poorly understood. Here, the brown alga Sargassum polycystum is used as a model to identify putative marine glacial refugia and explore biogeographical patterns driven by climate change in the late Pleistocene ice ages. Location South‐East Asia. Methods Mitochondrial cox1 and cox3 and nuclear internal transcribed spacer‐2 ( ITS 2) were obtained from 310, 325 and 313 individuals of S. polycystum (23 localities), respectively. Phylogenetic trees (maximum likelihood and Bayesian inference) and haplotype/ribotype networks were constructed to elucidate phylogeographical patterns. Analysis of molecular variance ( AMOVA ), neutrality tests (Tajima's D and Fu & Li's D* ), current (θ π ) and historical (θ w ) genetic diversities and extended Bayesian skyline plots ( EBSP ) were used to estimate historical demography. Results The populations from the south‐west of Hainan Island harboured much higher genetic diversity and unique endemism in comparison with other populations in the distribution range. Sargassum polycystum experienced relatively long‐term stable population size followed by a continued period of demographic expansion in the late Pleistocene. Main conclusions Our phylogeographical evidence revealed the existence of a previously unidentified marine refugium specific to S. polycystum in the south‐west of Hainan Island, China (the Central Depression of the Yinggehai Basin), along with a possible secondary refugium around the Bali Island, Indonesia. These biogeographical findings provide important insights regarding speciation, adaptation and evolution of marine organisms in South‐East Asia and the conservation of unique biodiversity under climate change.

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Association of MSI2 Gene Polymorphism with Age-at-Onset of Schizophrenia in a Chinese Population - Zhi-Lin Luan; Xiao-Hui Cui; Hu Xu; He-Yuan Lu; Yu-Yuan Li; Tian-Lan Lu; Dai Zhang (Neuroscience Bulletin, 2017)

Secretion of Down Syndrome Critical Region 1 Isoform 4 in Ischemic Retinal Ganglion Cells Displays Anti-Angiogenic Properties Via NFATc1-Dependent Pathway - Yue Xu; Boyu Yang; Yaguang Hu; Lin Lu; Xi Lu; Jiawei Wang; Qinmeng Shu; Qiaochu Cheng; Shanshan Yu; Fan Xu; Jingjing Huang; Xiaoling Liang (Molecular Neurobiology, 2017)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

The improvement of M1 polarization in macrophages by glycopeptide derived from Ganoderma lucidum - Li-Xin Sun; Zhi-Bin Lin; Jie Lu; Wei-Dong Li; Yan-Dong Niu; Yu Sun; Chen-Yang Hu; Guo-Qiang Zhang; Xin-Suo Duan (Immunologic Research, 2017)

Occurrence of 25 pharmaceuticals in Taihu Lake and their removal from two urban drinking water treatment plants and a constructed wetland - Xia-Lin Hu; Yi-Fan Bao; Jun-Jian Hu; You-Yu Liu; Da-Qiang Yin (Environmental Science and Pollution Research, 2017)
Pharmaceuticals in drinking water sources have raised significant concerns due to their persistent input and potential human health risks. The seasonal occurrence of 25 pharmaceuticals including 23 antibiotics, paracetamol (PAR), and carbamazepine (CMZ) in Taihu Lake was investigated; meanwhile, the distribution and removal of these pharmaceuticals in two drinking water treatment plants (DWTPs) and a constructed wetland were evaluated. A high detection frequency (>70%) in the Taihu Lake was observed for nearly all the 25 pharmaceutics. Chlortetracycline (234.7 ng L −1 ), chloramphenicol (27.1 ng L −1 ), erythromycin (72.6 ng L −1 ), PAR (71.7 ng L −1 ), and CMZP (23.6 ng L −1 ) are compounds with both a high detection frequency (100%) and the highest concentrations, suggesting their wide use in the Taihu Basin. Higher concentrations of chloramphenicols, macrolides, PAR, and CMZP were observed in dry season than in wet season, probably due to the low flow conditions of the lake in winter and the properties of pharmaceuticals. The overall contamination levels of antibiotic pharmaceutics (0.2–74.9 ng L −1 ) in the Taihu Lake were lower than or comparable to those reported worldwide. However, for nonantibiotic pharmaceutics, PAR (45.0 ng L −1 ) and CMZP (14.5 ng L −1 ), significantly higher concentrations were observed in the Taihu Lake than at a global scale. High detection frequencies of 25 pharmaceuticals were observed in both the two DWTPs (100%) and the wetland (>60%) except for florfenicol and sulfapyridine. The removal efficacies of the studied pharmaceuticals in DWTP B with advanced treatment processes including ozonation and granular activated carbon filtration (16.7–100%) were superior to DWTP A with conventional treatment processes (2.9–100%), except for sulfonamides. Wetland C with the constructed root channel technology was efficient (24.2–100%) for removing most pharmaceuticals. This work suggests that the application of cost-effective technologies such as constructed wetlands should be considered as an efficient alternative for removing pharmaceuticals from water supply sources.

RETRACTED ARTICLE: MicroRNA-20b suppresses the expression of ZFP-148 in viral myocarditis - Hong-Fei Xu; Xiang-Ting Gao; Jun-Yi Lin; Xue-Hua Xu; Jun Hu; Yu-Jie Ding; Shao-Hua Zhu (Molecular and Cellular Biochemistry, 2017)

Periodic increments in the jumbo squid (Dosidicus gigas) beak: a potential tool for determining age and investigating regional difference in growth rates - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu; Wei Yu; Jin Tao Wang; Jing Yuan Lin (Hydrobiologia, 2017)

Biotransformation of Rutin Using Crude Enzyme from Rhodopseudomonas palustris - Chun-jie Guan; Yu-jia Ji; Jia-lin Hu; Chao-nan Hu; Fei Yang; Guan-e Yang (Current Microbiology, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Coagulation increased the growth potential of various species bacteria of the effluent of a MBR for the treatment of domestic wastewater - Tong Yu; Guoqiang Li; Wenqi Lin; Hong-Ying Hu; Yun Lu (Environmental Science and Pollution Research, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

Detection of genotoxic effects of drinking water disinfection by-products using Vicia faba bioassay - Yu Hu; Li Tan; Shao-Hui Zhang; Yu-Ting Zuo; Xue Han; Na Liu; Wen-Qing Lu; Ai-Lin Liu (Environmental Science and Pollution Research, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Distribution, fractionation, and contamination assessment of heavy metals in offshore surface sediments from western Xiamen Bay, China - Qiuli Yang; Gongren Hu; Ruilian Yu; Haixing He; Chengqi Lin (Acta Geochimica, 2016)

Prey selection and foraging behavior of the whelk Rapana venosa - Nan Hu; Fang Wang; Tao Zhang; Hao Song; Zheng-Lin Yu; Da-Peng Liu (Marine Biology, 2016)

Synthesis and evaluation as potential antitumor agents of novel ursolic acid derivatives - Ming-Chuan Liu; Sheng-Jie Yang; Lin-Hong Jin; De-Yu Hu; Wei Xue; Song Yang (Medicinal Chemistry Research, 2016)

Regulation and the Mechanism of Estrogen on Cav1.2 Gene in Rat-Cultured Cortical Astrocytes - Ling He; Xiao-Tong Hu; Yu-Jie Lai; Yan Long; Lu Liu; Bing-lin Zhu; Guo-Jun Chen (Journal of Molecular Neuroscience, 2016)

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities - Qi-Lei Chen; Xi-Yu Chen; Lin Zhu; Hu-Biao Chen; Hing-Man Ho; Wing-Ping Yeung; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Onychomycosis Associated with Exophiala oligosperma in Taiwan - Yu-Min Wen; Ranjith Kumar Rajendran; Ying-Fang Lin; Roland Kirschner; Sindy Hu (Mycopathologia, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Soil taxonomy and distribution characteristics of the permafrost region in the Qinghai-Tibet Plateau, China - Hong-bing Fang; Lin Zhao; Xiao-dong Wu; Yu-guo Zhao; Yong-hua Zhao; Guo-jie Hu (Journal of Mountain Science, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Determination of squid age using upper beak rostrum sections: technique improvement and comparison with the statolith - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu (Marine Biology, 2015)

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Association of Enterovirus 71 encephalitis with the interleukin-8 gene region in Chinese children - Jian Li; Aiwei Lin; Chengwen Yu; Zhaofang Zhang; Daoyan Xu; Wei Hu; Liyan Liu; Shaoning Wang; Xiuzhen Nie; Wenhui Sun; Zhongtao Gai; Zongbo Chen (Infectious Diseases, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

JcCBF2 gene from Jatropha curcas improves freezing tolerance of Arabidopsis thaliana during the early stage of stress - Linghui Wang; Jihai Gao; Xiaobo Qin; Xiaodong Shi; Lin Luo; Guozhen Zhang; Hongwu Yu; Chenyang Li; Minchao Hu; Qifan Liu; Ying Xu; Fang Chen (Molecular Biology Reports, 2015)

Brittle failure of shale under uniaxial compression - Yan Chuanliang; Deng Jingen; Hu Lianbo; Chen Zijian; Yan Xinjiang; Lin Hai; Tan Qiang; Yu Baohua (Arabian Journal of Geosciences, 2015)

Neurochemical properties of the synapses between the parabrachial nucleus-derived CGRP-positive axonal terminals and the GABAergic neurons in the lateral capsular division of central nucleus of amygdala - Ya-Cheng Lu; Yan-Zhou Chen; Yan-Yan Wei; Xiao-Tao He; Xia Li; Wei Hu; Yuchio Yanagawa; Wen Wang; Sheng-Xi Wu; Yu-Lin Dong (Molecular Neurobiology, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

The capability of estuarine sediments to remove nitrogen: implications for drinking water resource in Yangtze Estuary - Lin Liu; Dongqi Wang; Huanguang Deng; Yangjie Li; Siqi Chang; Zhanlei Wu; Lin Yu; Yujie Hu; Zhongjie Yu; Zhenlou Chen (Environmental Science and Pollution Research, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Microscopic research on a multi-source traditional Chinese medicine, Astragali Radix - Kun-Zi Yu; Jing Liu; Bao-Lin Guo; Zhong-Zhen Zhao; Hao Hong; Hu-Biao Chen; Shao-Qing Cai (Journal of Natural Medicines, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Variability of atlantic meridional overturning circulation in FGOALS-g2 - Wenyu Huang; Bin Wang; Lijuan Li; Li Dong; Pengfei Lin; Yongqiang Yu; Tianjun Zhou; Li Liu; Shiming Xu; Kun Xia; Ye Pu; Lu Wang; et al. (Advances in Atmospheric Sciences, 2014)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

A geospatial web portal for sharing and analyzing greenhouse gas data derived from satellite remote sensing images - Hao Lin; Bailang Yu; Zuoqi Chen; Yingjie Hu; Yan Huang; Jianping Wu; Bin Wu; Rong Ge (Frontiers of Earth Science, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Preliminary evaluations of FGOALS-g2 for decadal predictions - Bin Wang; Mimi Liu; Yongqiang Yu; Lijuan Li; Pengfei Lin; Li Dong; Li Liu; Jiping Liu; Wenyu Huang; Shiming Xu; Si Shen; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Non-coding RNAs in Alzheimer's Disease - Lin Tan; Jin-Tai Yu; Nan Hu; Lan Tan (Molecular Neurobiology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Expression of Maize Gene Encoding C4-Pyruvate Orthophosphate Dikinase (PPDK) and C4-Phosphoenolpyruvate Carboxylase (PEPC) in Transgenic Arabidopsis - Yu-Min Wang; Wei-Gang Xu; Lin Hu; Lei Zhang; Yan Li; Xi-He Du (Plant Molecular Biology Reporter, 2012)

Dorsal root ganglion compression as an animal model of sciatica and low back pain - Xiao-Yu Lin; Jing Yang; Hui-Ming Li; San-Jue Hu; Jun-Ling Xing (Neuroscience Bulletin, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

An alternative method for cDNA cloning from surrogate eukaryotic cells transfected with the corresponding genomic DNA - Lin-yong Hu; Chen-chen Cui; Yu-jie Song; Xiang-guo Wang; Ya-ping Jin; Ai-hua Wang; Yong Zhang (Biotechnology Letters, 2012)

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells - Jing-Yu Lee; I-Chun Chien; Win-Yu Lin; Shao-min Wu; Bo-Huei Wei; Yu-En Lee; Hu-Hui Lee (Molecular and Cellular Biochemistry, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

Proteomic analysis of peritrophic membrane (PM) from the midgut of fifth-instar larvae, Bombyx mori - Xiaolong Hu; Lin Chen; Xingwei Xiang; Rui Yang; Shaofang Yu; Xiaofeng Wu (Molecular Biology Reports, 2012)

Autographa californica multiple nucleopolyhedrovirus odv-e25 (Ac94) is required for budded virus infectivity and occlusion-derived virus formation - Lin Chen; Xiaolong Hu; Xingwei Xiang; Shaofang Yu; Rui Yang; Xiaofeng Wu (Archives of Virology, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Haze detection, perfection and removal for high spatial resolution satellite imagery - Changbing Liu; Jianbo Hu; Yu Lin; Shihong Wu; Wei Huang (International Journal of Remote Sensing, 2011)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

A new alkaloid from the marine-derived fungus Hypocrea virens - Tao Liu; Zhan-Lin Li; Yu Wang; Li Tian; Yue-Hu Pei; Hui-Ming Hua (Natural Product Research, 2011)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Phylogeographic heterogeneity of the brown macroalga Sargassum horneri (Fucaceae) in the northwestern Pacific in relation to late Pleistocene glaciation and tectonic configurations - ZI‐MIN HU; SHINYA UWAI; SHEN‐HUI YU; TERUHISA KOMATSU; TETSURO AJISAKA; DE‐LIN DUAN (Molecular Ecology, 2011)
Pleistocene glacial oscillations and associated tectonic processes are believed to have influenced the historical abundances and distribution of organisms in the Asia Northwest Pacific (ANP). Accumulating evidence indicates that factors shaping tempospatial population dynamics and distribution patterns of marine taxa vary with biogeographical latitude, pelagic behaviour and oceanographic regimes. To detect what kinds of historical and contemporary factors affected genetic connectivity, phylogeographic profiles of littoral macroalga Sargassum horneri in the ANP were analysed based on mitochondrial (Cox3) and chloroplast ( rbc L) data sets. Five distinct clades were recovered. A strong signature of biogeographical structure was revealed (Φ CT = 0.487, P 0.0001) derived from remarkable differentiation in clade distribution, as clade I is restricted to Chinese marginal seas (Yellow–Bohai Sea, East China Sea and South China Sea), whereas clades II–V are discontinuously scattered around the main Islands of Japan. Furthermore, two secondary contact regions were identified along the south Japan‐Pacific coastline. This significant differentiation between the two basins may reflect historical glacial isolation in the northwestern Pacific, which is congruent with the estimates of clade divergence and demographic expansion during the late Quaternary low sea levels. Analysis of molecular variance and the population‐pair statistic F ST also revealed significant genetic structural differences between Chinese marginal seas and the Japanese basin. This exceptional phylogeographic architecture in S. horneri , initially shaped by historical geographic isolation during the late Pleistocene ice age and physical biogeographical barriers, can be complicated by oceanographic regimes (ocean surface currents) and relocating behaviour such as oceanic drifting.

Phytoplankton variation and its relationship with the environment in Xiangxi Bay in spring after damming of the Three-Gorges, China - Guangjie Zhou; Xuemin Zhao; Yonghong Bi; Yubin Liang; Jianlin Hu; Min Yang; Yu Mei; Kongxian Zhu; Lin Zhang; Zhengyu Hu (Environmental Monitoring and Assessment, 2011)

Nitroreductase-mediated Gonadal Dysgenesis for Infertility Control of Genetically Modified Zebrafish - Shao-Yang Hu; Pei-Yu Lin; Chia-Hsuan Liao; Hong-Yi Gong; Gen-Hwa Lin; Koichi Kawakami; Jen-Leih Wu (Marine Biotechnology, 2010)

Responses of soil chemical and biological properties to nitrogen addition in a Dahurian larch plantation in Northeast China - Ya-Lin Hu; De-Hui Zeng; Yun-Xia Liu; Yu-Lan Zhang; Zhen-Hua Chen; Zheng-Quan Wang (Plant and Soil, 2010)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

On the intensity and type transition of land use at the basin scale using RS/GIS: a case study of the Hanjiang River Basin - Guangming Yu; Qun Zeng; Shan Yang; Limei Hu; Xiaowei Lin; Yi Che; Yuge Zheng (Environmental Monitoring and Assessment, 2010)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

A complete mitochondrial genome of wheat (Triticum aestivum cv. Chinese Yumai), and fast evolving mitochondrial genes in higher plants - Peng Cui; Huitao Liu; Qiang Lin; Feng Ding; Guoyin Zhuo; Songnian Hu; Dongcheng Liu; Wenlong Yang; Kehui Zhan; Aimin Zhang; Jun Yu (Journal of Genetics, 2009)

Fabrication of a Novel Core-Shell Gene Delivery System Based on a Brush-Like Polycation of α, β–Poly (L-Aspartate-Graft-PEI) - Jia-Hui Yu; Ji-Shan Quan; Jung-Taek Kwon; Cheng-Xiong Xu; Bo Sun; Hu-Lin Jiang; Jae-Woon Nah; Eun-Mi Kim; Hwan-Jeong Jeong; Myung-Haing Cho; Chong-Su Cho (Pharmaceutical Research, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Assessing factors influencing vegetation coverage calculation with remote sensing imagery - Zhujun Gu; Zhiyuan Zeng; Xuezheng Shi; Lin Li; Dongsheng Yu; Wei Zheng; Zhenlong Zhang; Zifu Hu (International Journal of Remote Sensing, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Influence of N-Terminal Truncations on the Functional Expression of Bacillus licheniformis γ-Glutamyltranspeptidase in Recombinant Escherichia coli - Long-Liu Lin; Li-Yu Yang; Hui-Yu Hu; Huei-Fen Lo (Current Microbiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Overexpression of proline oxidase induces proline-dependent and mitochondria-mediated apoptosis - Chien-an A. Hu; Steven P. Donald; Jian Yu; Wei-Wen Lin; Zhihe Liu; Gary Steel; Cassandra Obie; David Valle; James M. Phang (Molecular and Cellular Biochemistry, 2007)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)

Phylogenetic Analysis and Biochemical Characterization of a Thermostable Dihydropyrimidinase from Alkaliphilic Bacillus sp. TS-23 - Long-Liu Lin; Wen-Hwei Hsu; Wei-Yi Hsu; Shu-Chen Kan; Hui-Yu Hu (Antonie van Leeuwenhoek, 2005)

Stabilization of a truncated Bacillus sp. strain TS-23 α-amylase by replacing histidine-436 with aspartate - Huei-Fen Lo; Ya-Hui Chen; Nai-Wan Hsiao; Hsiang-Ling Chen; Hui-Yu Hu; Wen-Hwei Hsu; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Replacement of Methionine 208 in a Truncated Bacillus sp. TS-23 α-Amylase with Oxidation-Resistant Leucine Enhances Its Resistance to Hydrogen Peroxide - Long-Liu Lin; Huei-Fen Lo; Wen-Ying Chiang; Hui-Yu Hu; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2003)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)